Laminate and composition for forming vertically aligned liquid crystal cured film
By directly forming a vertically oriented liquid crystal cured film of a polymerizable liquid crystal composition containing a vertical orientation accelerator on the substrate, and reacting a prereacting compound with the substrate surface to form a crosslinked structure, the problems of complex production process and low productivity in the prior art are solved, and efficient liquid crystal cured film manufacturing is achieved.
Patent Information
- Application Number
- CN202510216712.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-26
- Filing Date
- 2020-04-15
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art requires the formation of vertically oriented films when manufacturing vertically oriented liquid crystal cured films, resulting in complex production processes and low productivity.
In the case where the vertically oriented film is not formed, a vertically oriented liquid crystal cured film is formed directly on the substrate by using a polymerizable liquid crystal composition containing a vertical orientation promoter, and a crosslinked structure is formed to improve adhesion by reacting the pre-reacting compound with the surface of the substrate.
In the absence of a vertically oriented film, the optimal adhesion force between the vertically oriented liquid crystal cured film and the substrate and a moderate substrate peeling force are achieved, simplifying the manufacturing process and improving production efficiency.
Smart Images

Figure CN119828277A_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese invention patent application No. 202080027180.6 (PCT application number is PCT / JP2020 / 016519), whose application date is April 15, 2020 and whose invention name is “Laminate and vertically oriented liquid crystal curing film forming composition”. Technical Field
[0002] The present invention relates to a laminate including a vertically aligned liquid crystal cured film, an elliptically polarizing plate including the laminate, and an organic EL display device, and also to a composition for forming a vertically aligned liquid crystal cured film that can be used to form the laminate. Background Art
[0003] The elliptically polarizing plate is an optical component formed by stacking a polarizing plate and a phase difference plate, for example, in an organic EL image display device and other devices that display images in a planar state, it is used to prevent light reflection at the electrodes constituting the device. As a phase difference plate constituting the elliptically polarizing plate, a so-called λ / 4 plate is generally used. As such a phase difference plate, a phase difference plate formed by the following horizontally oriented liquid crystal solidification film is known, and the horizontally oriented liquid crystal solidification film is polymerized and solidified in a state where a polymerizable liquid crystal compound is oriented in a horizontal direction relative to the plane of the phase difference plate. In addition, it is known that by further assembling a vertically oriented liquid crystal solidification film into an elliptically polarizing plate having a horizontally oriented liquid crystal solidification film, the oblique hue change during the black display when the elliptically polarizing plate is used in an organic EL display device can be suppressed. Patent document 1 describes the following method: a vertically oriented film is formed on a substrate, and a composition containing a polymerizable liquid crystal compound is applied to the above-mentioned vertically oriented film, thereby forming a vertically oriented liquid crystal solidification film. The following laminate is described, which includes a vertically oriented liquid crystal solidification film formed and a horizontally oriented liquid crystal solidification film formed on a horizontally oriented film.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-57646 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, in the past, in order to manufacture a vertically oriented liquid crystal curing film, a vertically oriented film for orienting a polymerizable liquid crystal compound in a vertical direction was generally required. Therefore, a vertically oriented film needs to be formed before the formation of the vertically oriented liquid crystal curing film. In order to obtain a coating film from an alignment film forming composition and a liquid crystal curing film forming composition, at least 2 or more coating film forming processes are required, and there is a problem that productivity is easily reduced. In view of this, in order to improve productivity, a method for forming a vertically oriented liquid crystal curing film without forming a vertically oriented film is required. The inventor of the present application has developed and proposed a laminate, which includes a vertically oriented liquid crystal curing film directly formed on a substrate without forming a vertically oriented film. In this development, the following new discovery was obtained: when a compound with a vertically oriented control power is added to the vertically oriented liquid crystal curing film in order to form a vertically oriented liquid crystal curing film directly on a substrate without a vertically oriented film, the adhesion of the vertically oriented liquid crystal curing film to the substrate is easily reduced, and the substrate is prone to excessive peeling.
[0009] The present invention provides a novel solution to the above-mentioned problems, and aims to provide a laminated body in which a vertically aligned liquid crystal cured film formed without a vertically aligned film is laminated with a substrate with the most appropriate adhesion and exhibits the most appropriate substrate peeling strength.
[0010] Means for solving problems
[0011] The inventors of the present application have conducted intensive studies to solve the above-mentioned problems, and as a result, have completed the present invention. That is, the present invention includes the following aspects.
[0012] [1] A laminate comprising a substrate and a vertically aligned liquid crystal cured film adjacent to the substrate,
[0013] The vertically aligned liquid crystal cured film is a cured product of a polymerizable liquid crystal composition comprising at least one vertical alignment promoter and at least one polymerizable liquid crystal compound, and is a liquid crystal cured film formed by curing the polymerizable liquid crystal compound in a state of being aligned in a vertical direction relative to the plane of the liquid crystal cured film.
[0014] The laminate satisfies the formula (1).
[0015] 0.02 <P<1.00(N / 25mm) (1)
[0016] [In formula (1), P is the substrate peeling force (N / 25 mm) when the substrate is peeled off at a speed of 300 mm / min at the interface between the vertically aligned liquid crystal cured film and the substrate constituting the laminate.]
[0017] [2] The laminate according to [1] above, wherein the thickness of the vertically aligned liquid crystal cured film is 0.3 μm or more and 5.0 μm or less.
[0018] [3] The laminated body according to the above [1] or [2], wherein the vertically aligned liquid crystal cured film satisfies the formula (2).
[0019] -150nm≤RthC(550)≤-30nm (2)
[0020] [In formula (2), RthC(550) represents the phase difference value in the thickness direction of the vertically aligned liquid crystal cured film at a wavelength of 550 nm.]
[0021] [4] The laminate according to any one of [1] to [3] above, wherein the polymerizable liquid crystal compound has a (meth)acryloyl group as a polymerizable group.
[0022] [5] The laminate according to any one of [1] to [4] above, wherein the vertically aligned liquid crystal cured film contains an ionic compound composed of non-metal atoms as a vertical alignment promoter.
[0023] [6] The laminate according to [5] above, comprising the ionic compound composed of the non-metal atoms, wherein the molecular weight of the ionic compound is 100 to 10,000.
[0024] [7] A laminate as described in any one of [1] to [6] above, wherein the polymerizable liquid crystal composition that forms the vertically aligned liquid crystal cured film comprises at least one vertical alignment promoter, at least one polymerizable liquid crystal compound having a (meth)acryloyl group, and at least one polymerizable non-liquid crystal compound having two or more (meth)acryloyl groups.
[0025] [8] The laminate according to any one of [1] to [7] above, wherein the vertically aligned liquid crystal cured film contains a nonionic silane compound as a vertical alignment accelerator.
[0026] [9] The laminate according to [8] above, comprising the nonionic silane compound, wherein the nonionic silane compound is a silane coupling agent.
[0027]
[10] The laminate according to any one of [1] to [4] above, wherein the vertically aligned liquid crystal cured film contains a nonionic silane compound and an ionic compound composed of non-metal atoms as a vertical alignment promoter.
[0028]
[11] The laminate according to any one of [1] to
[10] above, wherein the vertically aligned liquid crystal cured film contains a compound having a functional group reactive with a hydroxyl group or a carboxyl group and a (meth)acryloyl group in the molecule.
[0029]
[12] The laminate according to any one of [1] to
[11] above, wherein the vertically aligned liquid crystal cured film satisfies the following relational expression (3).
[0030] RthC(450) / RthC(550)≤1.0 (3)
[0031] [In formula (3), RthC(450) represents the phase difference value in the thickness direction of the vertically aligned liquid crystal cured film at a wavelength of 450 nm, and RthC(550) represents the phase difference value in the thickness direction of the vertically aligned liquid crystal cured film at a wavelength of 550 nm.]
[0032]
[13] The laminate according to any one of [1] to
[12] above, further comprising a horizontally aligned retardation film.
[0033]
[14] The laminated body according to
[13] above, wherein the horizontally aligned retardation film is a horizontally aligned liquid crystal cured film obtained by curing at least one polymerizable liquid crystal compound in a state of being horizontally aligned with respect to the in-plane direction of the retardation film.
[0034]
[15] An elliptically polarizing plate comprising a polarizing film and the laminate according to
[13] or
[14] above.
[0035]
[16] The elliptically polarizing plate as described in
[15] above, wherein the angle formed by the slow axis of the horizontally oriented phase difference film and the absorption axis of the polarizing film is 45±5°.
[0036]
[17] An organic EL display device comprising the elliptically polarizing plate described in
[15] or
[16] above.
[0037]
[18] A composition for forming a vertically aligned liquid crystal cured film, comprising:
[0038] At least one selected from the group consisting of a compound having a functional group capable of reacting with a hydroxyl group or a carboxyl group and a (meth)acryloyl group in the molecule, and a polymerizable non-liquid crystal compound having two or more (meth)acryloyl groups;
[0039] a polymerizable liquid crystal compound; and
[0040] An ionic compound composed of non-metal atoms that acts as a vertical alignment promoter.
[0041]
[19] The composition for forming a vertically aligned liquid crystal cured film according to the above
[18] , wherein the polymerizable liquid crystal compound is a polymerizable liquid crystal compound having a (meth)acryloyl group.
[0042] Effects of the Invention
[0043] According to the present invention, a laminated body in which a vertically aligned liquid crystal cured film formed without a vertically aligned film and a substrate are laminated with optimal adhesion and exhibits optimal substrate peeling strength can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] [ Figure 1 ] is a schematic cross-sectional view showing an example of the layer structure of the laminate of the present invention. DETAILED DESCRIPTION
[0045] The laminate of the present invention comprises a vertically aligned liquid crystal cured film and a substrate. In the present invention, the vertically aligned liquid crystal cured film is laminated on the substrate without the vertically aligned film, and the substrate and the vertically aligned liquid crystal cured film exist adjacent to each other. In the present invention, in the laminate of the present invention, the vertically aligned liquid crystal cured film can be formed without the vertically aligned film, so the number of manufacturing steps of the laminate is reduced, and the laminate can be manufactured with good productivity.
[0046] Figure 1 One embodiment of the laminate of the present invention is shown, and the most basic layer structure of the laminate of the present invention is shown, but the present invention is not limited thereto. Figure 1 The laminated body 11 shown is formed by laminating a substrate 1 and a vertically aligned liquid crystal cured film 2 . Figure 1 In the laminate 11 shown, the vertically oriented liquid crystal curing film 2 is directly formed on the substrate 1 without a layer having a vertical orientation control force (hereinafter, also referred to as a "vertical orientation film"), and the substrate 1 is adjacent to the vertically oriented liquid crystal curing film 2. The laminate of the present invention can be composed of other layers in addition to the substrate and the vertically oriented liquid crystal curing film. As other layers, there can be cited a horizontally oriented phase difference film (horizontally oriented liquid crystal curing film), a horizontally oriented film, a protective layer, a hard coating layer and other cured resin layers, and an adhesive layer for bonding the laminate of the present invention to a polarizing film, etc.
[0047] The laminated body of the present invention satisfies the following formula (1).
[0048] 0.02 <P<1.00(N / 25mm) (1)
[0049] In the formula (1), P is a substrate peeling force (N / 25 mm) when the substrate is peeled off at a rate of 300 mm / min at the interface between the vertically aligned liquid crystal cured film and the substrate constituting the laminate.
[0050] In the present invention, a vertically oriented liquid crystal curing film is formed directly on a substrate without a vertically oriented film. The polymerizable liquid crystal composition (hereinafter, also referred to as a "vertical alignment liquid crystal curing film forming composition") used to form the above-mentioned vertically oriented liquid crystal curing film contains a vertical alignment promoter, and is designed to exhibit a vertical alignment control force that orients the polymerizable liquid crystal compound contained in the composition in a vertical direction relative to the coating film plane when applied to the substrate. In the present invention, in order to exhibit a vertical alignment control force, the vertically oriented liquid crystal curing film forming composition may contain a vertically oriented liquid crystal curing film at the interface ( Figure 1 Interface a in: hereinafter also referred to as "substrate-side interface"), a component (such as an ionic compound formed by non-metallic atoms as described later) that generates electrostatic repulsion to the polymerizable liquid crystal compound is used as a vertical alignment promoter. However, when the composition for forming a vertically aligned liquid crystal solidified film is applied to a substrate, such a component that generates electrostatic repulsion is prone to segregation at the substrate-side interface. In addition, such a component that generates electrostatic repulsion generally does not have a polymerizable group, and a network structure cannot be formed between the components, or between the components and the polymerizable liquid crystal compound that forms the vertically aligned liquid crystal solidified film. Therefore, there is a tendency that coagulation failure is prone to occur at the substrate-side interface of the segregated vertically aligned liquid crystal solidified film. For a laminate including a vertically aligned liquid crystal solidified film directly formed on a substrate, coagulation failure is prone to occur near the substrate-side interface where the vertically aligned liquid crystal solidified film is segregated during the cutting process, and the vertically aligned liquid crystal solidified film is easily peeled off from the substrate, thereby causing bulging and peeling at the end of the laminate to cause product defects, so it is necessary to improve the adhesion between the vertically aligned liquid crystal solidified film and the substrate.
[0051] When the substrate peeling force P in the laminate of the present invention is less than 0.02, the adhesion between the substrate and the vertically oriented liquid crystal curing film is insufficient, and it is difficult to fully suppress the vertically oriented liquid crystal curing film from being peeled off from the substrate during the cutting process of the laminate. On the other hand, when the substrate peeling force is more than 1.00, the adhesion between the substrate and the vertically oriented liquid crystal curing film becomes too high, and a large force is required to peel the substrate from the laminate. In addition, it is difficult to cleanly peel the substrate and the vertically oriented liquid crystal curing film without generating residues on each other. When the laminate of the present invention satisfies the above formula (1), it becomes the following laminate: in the laminate, the substrate and the vertically oriented liquid crystal curing film adjacent to it are stacked with appropriate adhesion, and when the laminate is cut, the vertically oriented liquid crystal curing film is not easy to peel off from the substrate, but when the substrate is peeled off from the laminate, the substrate and the vertically oriented liquid crystal curing film can be cleanly peeled off with a smaller force. In the present invention, the substrate peeling force P is preferably 0.03 N / 25 mm or more, more preferably 0.035 N / 25 mm or more, and further preferably 0.04 N / 25 mm or more, and is preferably 0.8 N / 25 mm or less, more preferably 0.6 N / 25 mm or less, and further preferably 0.5 N / 25 mm or less.
[0052] It should be noted that the substrate peeling force P can be measured according to the method described in the examples described later.
[0053] The substrate peeling force P of the laminate can be controlled by selecting the composition of the vertically aligned liquid crystal cured film-forming composition for forming the vertically aligned liquid crystal cured film and the type of the substrate, particularly the surface state of the substrate.
[0054] Hereinafter, each structure of the laminated body of the present invention will be described in detail.
[0055] 〔Vertical alignment liquid crystal cured film〕
[0056] The vertically oriented liquid crystal curing film constituting the laminate of the present invention is a cured product of a polymerizable liquid crystal composition comprising at least one vertical orientation promoter and at least one polymerizable liquid crystal compound. In addition, the vertically oriented liquid crystal curing film is a liquid crystal curing film formed by curing the polymerizable liquid crystal compound in a state of being oriented in a vertical direction relative to the plane of the liquid crystal curing film. In the present invention, the vertically oriented liquid crystal curing film includes a vertical orientation promoter. That is, in the present invention, the vertically oriented liquid crystal curing film forming composition (polymerizable liquid crystal composition) forming the vertically oriented liquid crystal curing film includes a vertical orientation promoter. In the present invention, the so-called vertical orientation promoter refers to a material that promotes the polymerizable liquid crystal compound to perform liquid crystal orientation in a direction perpendicular to the film plane. By making the vertically oriented liquid crystal curing film include a vertical orientation promoter, a vertically oriented liquid crystal curing film can be formed without a vertically oriented film. Thus, in the laminate of the present invention, there is no need to form a vertically oriented liquid crystal curing film, the manufacturing process of the laminate is simplified, and the laminate can be manufactured with good productivity.
[0057] Examples of the vertical alignment promoter include: a component that generates electrostatic repulsion on the polymerizable liquid crystal compound at the interface on the substrate side when the composition is applied on the substrate (for example, the ionic compound described below); or a component that, when the composition is applied on the substrate, reduces the surface energy at the interface on the opposite side of the vertically aligned liquid crystal cured film to the substrate, thereby exerting a vertical alignment controlling force that orients the polymerizable liquid crystal compound in a vertical direction relative to the film plane (for example, the nonionic silane compound described below).
[0058] In the present invention, the composition for forming a vertically oriented liquid crystal solidified film preferably includes a component that generates electrostatic repulsion to the polymerizable liquid crystal compound at the interface of the substrate side when the composition is applied to the substrate as a vertical orientation promoter for promoting the orientation of the polymerizable liquid crystal compound in the vertical direction. As such a component, for example, an ionic compound can be cited. From the viewpoint of suppressing the generation of orientation defects in the vertically oriented liquid crystal solidified film, as a vertical orientation promoter, it is preferably included an ionic compound formed by non-metallic atoms. When the composition for forming a vertically oriented liquid crystal solidified film includes an ionic compound formed by non-metallic atoms, in the dried film formed by the composition, a vertical orientation control force for the polymerizable liquid crystal compound is presented by electrostatic interaction, and the polymerizable liquid crystal compound can be oriented in the vertical direction relative to the film plane in the dried film. Thus, the liquid crystal solidified film can be formed by maintaining the state of vertical orientation of the polymerizable liquid crystal compound.
[0059] As an ionic compound formed by a non-metallic atom (hereinafter, also referred to as "ionic compound"), for example, an onium salt (more specifically, a quaternary ammonium salt, a tertiary sulfonium salt, and a quaternary phosphonium salt having a positive charge on a nitrogen atom, etc.) can be cited. Among these onium salts, from the viewpoint of being able to further improve the vertical orientation of the polymerizable liquid crystal compound, a quaternary onium salt is preferred, and from the viewpoint of improving availability and mass production, a quaternary phosphonium salt or a quaternary ammonium salt is more preferred. The onium salt may have two or more quaternary onium salt sites in the molecule, or may be an oligomer or a polymer.
[0060] The molecular weight of the ionic compound is preferably 100 to 10,000. When the molecular weight is within the above range, it is easy to improve the vertical alignment of the polymerizable liquid crystal compound while ensuring the coating property of the composition for forming a vertically aligned liquid crystal cured film. The molecular weight of the ionic compound is more preferably 5000 or less, and further preferably 3000 or less.
[0061] As the cationic component of the ionic compound, for example, inorganic cations and organic cations can be cited. Among them, organic cations are preferred from the perspective of not being easy to produce orientation defects of polymerizable liquid crystal compounds. As organic cations, for example, imidazolium cations, pyridinium cations, ammonium cations, sulfonium cations and phosphonium cations can be cited.
[0062] Ionic compounds usually have counter anions. As anionic components that become counter ions of the above-mentioned cationic components, for example, inorganic anions and organic anions can be cited. Among them, from the aspect of not being easy to produce the orientation defects of polymerizable liquid crystal compounds, organic anions are preferred. It should be noted that cations and anions do not necessarily correspond one to one.
[0063] Specific examples of the anion component include the following anions.
[0064] Chloride anion - 〕、
[0065] Bromide anion 〔Br - 〕、
[0066] Iodide anion - 〕、
[0067] Tetrachloroaluminate anion 〔AlCl4 - 〕、
[0068] Heptachlorodialuminate anion〔Al2Cl7 - 〕、
[0069] Tetrafluoroborate anion 〔BF4 - 〕、
[0070] Hexafluorophosphate anion 〔PF6 - 〕、
[0071] Perchlorate anion 〔ClO4 - 〕、
[0072] Nitrate anion 〔NO3 - 〕、
[0073] Acetate anion 〔CH3COO - 〕、
[0074] trifluoroacetate anion 〔CF3COO - 〕、
[0075] Fluorosulfonate anion 〔FSO3 - 〕、
[0076] Methanesulfonate anion 〔CH3SO3 - 〕、
[0077] trifluoromethanesulfonate anion 〔CF3SO3 - 〕、
[0078] p-Toluenesulfonate anion 〔p-CH3C6H4SO3 - 〕、
[0079] Bis(fluorosulfonyl)imide anion〔(FSO2)2N - 〕、
[0080] Bis(trifluoromethanesulfonyl)imide anion〔(CF3SO2)2N - 〕、
[0081] Tris(trifluoromethanesulfonyl)methane anion〔(CF3SO2)3C - 〕、
[0082] Hexafluoroarsenate anion 〔AsF6 - 〕、
[0083] Hexafluoroantimonate anion 〔SbF6 - 〕、
[0084] Hexafluoroniobate anion〔NbF6 - 〕、
[0085] Hexafluorotantalate anion 〔TaF6 - 〕、
[0086] Dimethylphosphinate anion〔(CH3)2POO - 〕、
[0087] (poly)hydrofluorofluoride anion〔F(HF) n - 〕(for example, n represents an integer from 1 to 3),
[0088] Dicyanamide anion〔(CN)2N - 〕、
[0089] SCN - 〕、
[0090] Perfluorobutanesulfonate anion 〔C4F9SO3 - 〕、
[0091] Bis(pentafluoroethanesulfonyl)imide anion〔(C2F5SO2)2N - 〕、
[0092] Perfluorobutyrate anion 〔C3F7COO - 〕,and
[0093] (Trifluoromethanesulfonyl)(trifluoromethanecarbonyl)imide anion
[0094] 〔(CF3SO2)(CF3CO)N - 〕.
[0095] Specific examples of the ionic compound can be appropriately selected from the above-mentioned combinations of cationic components and anionic components. Specific examples of the compound of the combination of a cationic component and anionic component include the following compounds.
[0096] (Pyridinium salt)
[0097] N-hexylpyridinium hexafluorophosphate,
[0098] N-octylpyridinium hexafluorophosphate,
[0099] N-methyl-4-hexylpyridinium hexafluorophosphate,
[0100] N-butyl-4-methylpyridinium hexafluorophosphate,
[0101] N-octyl-4-methylpyridinium hexafluorophosphate,
[0102] Bis(fluorosulfonyl)imide N-hexylpyridinium,
[0103] Bis(fluorosulfonyl)imide N-octylpyridinium,
[0104] N-methyl-4-hexylpyridinium bis(fluorosulfonyl)imide,
[0105] N-butyl-4-methylpyridinium bis(fluorosulfonyl)imide,
[0106] Bis(fluorosulfonyl)imide N-octyl-4-methylpyridinium,
[0107] N-hexylpyridinium bis(trifluoromethanesulfonyl)imide,
[0108] N-octylpyridinium bis(trifluoromethanesulfonyl)imide,
[0109] N-methyl-4-hexylpyridinium bis(trifluoromethanesulfonyl)imide,
[0110] N-butyl-4-methylpyridinium bis(trifluoromethanesulfonyl)imide,
[0111] Bis(trifluoromethanesulfonyl)imide N-octyl-4-methylpyridinium,
[0112] N-hexylpyridinium p-toluenesulfonate,
[0113] N-Octylpyridinium p-toluenesulfonate,
[0114] N-methyl-4-hexylpyridinium p-toluenesulfonate,
[0115] N-butyl-4-methylpyridinium p-toluenesulfonate, and
[0116] N-Octyl-4-methylpyridinium p-toluenesulfonate.
[0117] (Imidazolium salt)
[0118] 1-Ethyl-3-methylimidazolium hexafluorophosphate,
[0119] 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide,
[0120] 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide,
[0121] 1-Ethyl-3-methylimidazolium p-toluenesulfonate,
[0122] 1-Butyl-3-methylimidazolium methanesulfonate, etc.
[0123] (Pyrrolidinium salt)
[0124] N-butyl-N-methylpyrrolidinium hexafluorophosphate,
[0125] Bis(fluorosulfonyl)imide N-butyl-N-methylpyrrolidinium,
[0126] N-butyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide,
[0127] N-butyl-N-methylpyrrolidinium p-toluenesulfonate, etc.
[0128] (Ammonium salt)
[0129] Tetrabutylammonium hexafluorophosphate,
[0130] Tetrabutylammonium bis(fluorosulfonyl)imide,
[0131] Tetrahexyl ammonium bis(fluorosulfonyl)imide,
[0132] Bis(fluorosulfonyl)imide trioctylmethylammonium,
[0133] Bis(fluorosulfonyl)imide (2-hydroxyethyl)trimethylammonium,
[0134] Tetrabutylammonium bis(trifluoromethanesulfonyl)imide,
[0135] Tetrahexylammonium bis(trifluoromethanesulfonyl)imide,
[0136] Bis(trifluoromethanesulfonyl)imide trioctylmethylammonium,
[0137] Bis(trifluoromethanesulfonyl)imide (2-hydroxyethyl)trimethylammonium,
[0138] Tetrabutylammonium p-toluenesulfonate,
[0139] Tetrahexyl ammonium p-toluenesulfonate,
[0140] Trioctylmethylammonium p-toluenesulfonate,
[0141] (2-Hydroxyethyl)trimethylammonium p-toluenesulfonate,
[0142] (2-Hydroxyethyl)trimethylammonium dimethylphosphinate,
[0143] Bis(trifluoromethanesulfonyl)imide 1-(3-trimethoxysilylpropyl)-1,1,1-tributylammonium,
[0144] 1-(3-trimethoxysilylpropyl)-1,1,1-trimethylammonium bis(trifluoromethanesulfonyl)imide,
[0145] Bis(trifluoromethanesulfonyl)imide 1-(3-trimethoxysilylbutyl)-1,1,1-tributylammonium,
[0146] 1-(3-trimethoxysilylbutyl)-1,1,1-trimethylammonium bis(trifluoromethanesulfonyl)imide,
[0147] Bis(trifluoromethanesulfonyl)imide N-{(3-triethoxysilylpropyl)carbamoyloxyethyl)}-N,N,N-trimethylammonium, and
[0148] Bis(trifluoromethanesulfonyl)imide N-[2-{3-(3-trimethoxysilylpropylamino)-1-oxopropoxy}ethyl]-N,N,N-trimethylammonium.
[0149] (Phosphonium salt)
[0150] Bis(trifluoromethanesulfonyl)imide tributyl(2-methoxyethyl)phosphonium,
[0151] Bis(trifluoromethanesulfonyl)imide tributylmethylphosphonium,
[0152] 1,1,1-trimethyl-1-[(trimethoxysilyl)methyl]phosphonium bis(trifluoromethanesulfonyl)imide,
[0153] 1,1,1-trimethyl-1-[2-(trimethoxysilyl)ethyl]phosphonium bis(trifluoromethanesulfonyl)imide,
[0154] 1,1,1-trimethyl-1-[3-(trimethoxysilyl)propyl]phosphonium bis(trifluoromethanesulfonyl)imide,
[0155] 1,1,1-trimethyl-1-[4-(trimethoxysilyl)butyl]phosphonium bis(trifluoromethanesulfonyl)imide,
[0156] 1,1,1-tributyl-1-[(trimethoxysilyl)methyl]phosphonium bis(trifluoromethanesulfonyl)imide,
[0157] 1,1,1-tributyl-1-[2-(trimethoxysilyl)ethyl]phosphonium bis(trifluoromethanesulfonyl)imide, and
[0158] 1,1,1-tributyl-1-[3-(trimethoxysilyl)propyl]phosphonium bis(trifluoromethanesulfonyl)imide.
[0159] These ionic compounds may be used alone or in combination of two or more. Among them, ionic compounds composed of phosphonium salts, pyridinium salts, and ammonium salts are preferred.
[0160] From the viewpoint of being able to further improve the vertical alignment of the polymerizable liquid crystal compound, the ionic compound preferably has Si element and / or F element in the molecular structure of the cationic part. When the ionic compound has Si element and / or F element in the molecular structure of the cationic part, it is easy to segregate the ionic compound on the surface of the vertically aligned liquid crystal cured film. Among them, as ionic compounds whose constituent elements are all non-metallic elements, the following ionic compounds (i) to (iii) are preferred.
[0161] (Ionic compound (i))
[0162]
[0163] (Ionic compound (ii))
[0164]
[0165] (Ionic compound (iii))
[0166]
[0167] For example, the vertical orientation of the polymerizable liquid crystal compound can be further improved by treating the surface of the substrate with a surfactant having a long alkyl group of a certain chain length to improve the orientation of the liquid crystal (for example, see Chapter 2 of "Liquid Crystal Handbook" Orientation and Physical Properties of Liquid Crystals (published by Maruzen Co., Ltd.)). That is, by treating the surface of the substrate with an ionic compound having a long alkyl group of a certain chain length, the vertical orientation of the polymerizable liquid crystal compound can be effectively improved.
[0168] Specifically, the ionic compound preferably satisfies the following formula (4).
[0169] 5 <M<16 (4)
[0170] In formula (4), M is represented by the following formula (5).
[0171] M = (the number of covalent bonds from the positively charged atom to the molecular chain terminal of the substituent with the largest number of covalent bonds to the molecular chain terminal among the substituents directly bonded to the positively charged atom) ÷ (the number of positively charged atoms) (5)
[0172] When the ionic compound satisfies the above-mentioned (4), the vertical alignment property of the polymerizable liquid crystal compound can be effectively improved.
[0173] It should be noted that, when there are two or more atoms with positive charge in the molecule of the ionic compound, for a substituent having two or more atoms with positive charge, the number of covalent bonds from the atom with positive charge regarded as the base point to the closest other atom with positive charge is taken as the "number of covalent bonds from the atom with positive charge to the end of the molecular chain" described in the above definition of M. In addition, when the ionic compound is an oligomer or polymer having two or more repeating units, the constituent unit is regarded as one molecule and the above M is calculated. When the atom with positive charge is incorporated in a ring structure, the number of covalent bonds from the atom with positive charge via the ring structure or the number of covalent bonds to the end of the substituent bonded to the ring structure, whichever has more covalent bonds, is taken as the "number of covalent bonds from the atom with positive charge to the end of the molecular chain" described in the above definition of M.
[0174] When the composition for forming a vertically aligned liquid crystal curing film contains an ionic compound formed by non-metallic atoms, its content is usually preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and further preferably 0.1 parts by mass or more relative to 100 parts by mass of the polymerizable liquid crystal compound contained in the composition for forming a vertically aligned liquid crystal curing film, and is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, and further preferably 3 parts by mass or less. When the content of the ionic compound formed by non-metallic atoms is within the above range, the good coating property of the composition for forming a vertically aligned liquid crystal curing film can be maintained, and the vertical alignment of the polymerizable liquid crystal compound can be effectively promoted.
[0175] The composition for forming a vertically aligned liquid crystal cured film preferably contains a component as a vertical alignment promoter that can exert a vertical alignment control force by reducing the interface ( Figure 1 The surface energy at the interface b in (hereinafter also referred to as the "non-substrate side interface") is adjusted so that the polymerizable liquid crystal compound is oriented in a vertical direction relative to the film plane. As such a component, for example, nonionic silane compounds can be cited. When the composition for forming a vertically oriented liquid crystal curing film contains a nonionic silane compound, there is a tendency that the nonionic silane compound reduces the surface tension of the composition for forming a vertically oriented liquid crystal curing film, and in the dried coating formed by the composition, the nonionic silane compound is biased at the interface between the dried coating and the air, which can improve the vertical orientation control force of the polymerizable liquid crystal compound, and make the polymerizable liquid crystal compound oriented in a vertical direction relative to the film plane in the dried coating. As a result, the liquid crystal curing film can be formed by maintaining the vertical orientation state of the polymerizable liquid crystal compound.
[0176] Nonionic silane compounds are nonionic compounds containing Si elements. As nonionic silane compounds, for example, silicone polymers such as polysilane, silicone resins such as silicone oil and silicone resins, and organosilicon oligomers, organic inorganic silane compounds such as silsesquioxane and alkoxysilane (more specifically, silane coupling agents, etc.) can be cited. These nonionic silane compounds can be used alone or in combination of two or more. Among them, from the viewpoint of further improving the adhesion with the adjacent layer, preferred silane coupling agents.
[0177] The nonionic silane compound may be a silicone monomer type or a silicone oligomer (polymer) type. When the silicone oligomer is represented in the form of a (monomer)-(monomer) copolymer, examples include: copolymers containing a mercaptopropyl group such as 3-mercaptopropyltrimethoxysilane-tetramethoxysilane copolymer, 3-mercaptopropyltrimethoxysilane-tetraethoxysilane copolymer, 3-mercaptopropyltriethoxysilane-tetramethoxysilane copolymer, and 3-mercaptopropyltriethoxysilane-tetraethoxysilane copolymer; and copolymers containing a mercaptopropyl group such as mercaptomethyltrimethoxysilane-tetramethoxysilane copolymer, mercaptomethyltrimethoxysilane-tetraethoxysilane copolymer, mercaptomethyltriethoxysilane-tetramethoxysilane copolymer, and mercaptomethyltriethoxysilane-tetraethoxysilane copolymer. 3-methacryloxypropyl trimethoxysilane-tetramethoxysilane copolymer, 3-methacryloxypropyl trimethoxysilane-tetraethoxysilane copolymer, 3-methacryloxypropyl triethoxysilane-tetramethoxysilane copolymer, 3-methacryloxypropyl triethoxysilane-tetraethoxysilane copolymer, 3-methacryloxypropyl methyl dimethoxysilane-tetramethoxysilane copolymer, 3-methacryloxypropyl methyl dimethoxysilane-tetraethoxysilane copolymer, 3-methacryloxypropyl methyl diethoxysilane-tetramethoxysilane copolymer and 3-methacryloxypropyl methyl Copolymers containing methacryloxypropyl groups such as diethoxysilane-tetraethoxysilane copolymers; 3-acryloxypropyl trimethoxysilane-tetramethoxysilane copolymers, 3-acryloxypropyl trimethoxysilane-tetraethoxysilane copolymers, 3-acryloxypropyl triethoxysilane-tetramethoxysilane copolymers, 3-acryloxypropyl triethoxysilane-tetraethoxysilane copolymers, 3-acryloxypropyl methyldimethoxysilane-tetramethoxysilane copolymers, 3-acryloxypropyl methyldimethoxysilane-tetraethoxysilane copolymers, 3-acryloxypropyl methyldiethoxysilane-tetramethoxysilane copolymers and Copolymers containing an acryloxypropyl group such as 3-acryloxypropylmethyldiethoxysilane-tetraethoxysilane copolymer; copolymers containing a vinyl group such as vinyltrimethoxysilane-tetramethoxysilane copolymer, vinyltrimethoxysilane-tetraethoxysilane copolymer, vinyltriethoxysilane-tetramethoxysilane copolymer, vinyltriethoxysilane-tetraethoxysilane copolymer, vinylmethyldimethoxysilane-tetramethoxysilane copolymer, vinylmethyldimethoxysilane-tetraethoxysilane copolymer, vinylmethyldiethoxysilane-tetramethoxysilane copolymer, and vinylmethyldiethoxysilane-tetraethoxysilane copolymer;Copolymers containing amino groups such as 3-aminopropyltrimethoxysilane-tetramethoxysilane copolymer, 3-aminopropyltrimethoxysilane-tetraethoxysilane copolymer, 3-aminopropyltriethoxysilane-tetramethoxysilane copolymer, 3-aminopropyltriethoxysilane-tetraethoxysilane copolymer, 3-aminopropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-aminopropylmethyldimethoxysilane-tetraethoxysilane copolymer, 3-aminopropylmethyldiethoxysilane-tetramethoxysilane copolymer and 3-aminopropylmethyldiethoxysilane-tetraethoxysilane copolymer. ;
[0178] Silane coupling agent is a compound containing Si element, and it has at least one functional group selected from the group consisting of vinyl, epoxy, styryl, methacrylic group, acrylic group, amino, isocyanurate, urea, sulfydryl, isocyanate, carboxyl, and hydroxyl at the end, and at least one alkoxysilyl or silanol group. By appropriately selecting these functional groups, it is possible to give the mechanical strength of the vertically oriented liquid crystal curing film to be improved, the surface modification of the vertically oriented liquid crystal curing film, and the specific effects of the adhesion of the layer adjacent to the vertically oriented liquid crystal curing film. From the viewpoint of adhesion, silane coupling agent is preferably a silane coupling agent with an alkoxysilyl and another different reactive group (for example, the above-mentioned functional group). Silane coupling agent is further preferably a silane coupling agent with an alkoxysilyl and a polar group. When the silane coupling agent has at least one alkoxysilyl and at least one polar group in its molecule, the vertical orientation of the polymerizable liquid crystal compound is easily further improved, and the tendency of the vertical orientation promotion effect can be significantly obtained. Examples of the polar group include an epoxy group, an amino group, an isocyanurate group, a mercapto group, a carboxyl group, and a hydroxyl group. In addition, the polar group may have a substituent or a protective group as appropriate in order to control the reactivity of the silane coupling agent.
[0179] Specific examples of the silane coupling agent include vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(2-methoxyethoxy)silane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyldimethoxymethylsilane, and 3-glycidoxypropylethoxydimethylsilane.
[0180] Examples of commercially available silane coupling agents include KP321, KP323, KP324, KP326, KP340, KP341, X22-161A, KF6001, KBM-1003, KBE-1003, KBM-303, KBM-402, KBM-403, KBE-402, KBE-403, KBM-1403, KBM-502, and KBM-503. Silane coupling agents manufactured by Shin-Etsu Chemical Co., Ltd. such as KBE-502, KBE-503, KBM-5103, KBM-602, KBM-603, KBM-903, KBE-903, KBE-9103, KBM-573, KBM-575, KBM-9659, KBE-585, KBM-802, KBM-803, KBE-846, and KBE-9007.
[0181] When the composition for forming a vertically aligned liquid crystal curing film includes a nonionic silane compound, its content is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and further preferably 0.1 parts by mass or more, relative to 100 parts by mass of the polymerizable liquid crystal compound contained in the polymerizable liquid crystal composition contained in the vertically aligned liquid crystal curing film forming composition. In addition, it is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, and further preferably 3 parts by mass or less. When the content of the nonionic silane compound is within the above range, it is possible to maintain the good coating property of the polymerizable liquid crystal composition and effectively promote the vertical alignment of the polymerizable liquid crystal compound.
[0182] In the present invention, the vertically oriented liquid crystal curing film preferably includes at least one of an ionic compound formed by non-metallic atoms and a non-ionic silane compound as a vertical orientation promoter, more preferably includes an ionic compound formed by non-metallic atoms as a vertical orientation promoter, and more preferably includes both an ionic compound formed by non-metallic atoms and a non-ionic silane compound as a vertical orientation promoter. The vertically oriented liquid crystal curing film comprises both an ionic compound formed by non-metallic atoms and a non-ionic silane compound. In the dried coating formed by the composition for forming a vertically oriented liquid crystal curing film, the electrostatic interaction of the ionic compound formed by non-metallic atoms at the interface on the substrate side and the surface energy reduction effect of the non-ionic silane compound at the interface on the non-substrate side are used to generate a vertical orientation control force for the polymerizable liquid crystal compound at the two interfaces of the liquid crystal curing film, so it is easy to further promote the vertical orientation of the polymerizable liquid crystal compound. Thus, it is possible to maintain a state in which the polymerizable liquid crystal compound is more accurately oriented vertically to form a liquid crystal curing film.
[0183] The vertical alignment liquid crystal cured film is a cured product of a polymerizable liquid crystal composition that includes at least one polymerizable liquid crystal compound in addition to the above-mentioned vertical alignment promoter. In the present invention, the polymerizable liquid crystal compound included in the vertical alignment liquid crystal cured film forming composition (polymerizable liquid crystal composition) that forms the vertical alignment liquid crystal cured film refers to a liquid crystal compound having a polymerizable group. The polymerizable liquid crystal compound is not particularly limited, and for example, a polymerizable liquid crystal compound previously known in the field of phase difference film can be used.
[0184] A polymerizable group refers to a group that can participate in a polymerization reaction through an active free radical, an acid, etc. generated by a polymerization initiator. As a polymerizable group, for example, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, (meth)acryloyloxy, oxirane, oxetanyl, etc. can be cited. Among them, from the perspective of being able to construct a network structure with a compound having a functional group that can react with a hydroxyl or carboxyl group in the molecule and / or a polymerizable non-liquid crystal compound having more than two (meth)acryloyl groups, and effectively improving the adhesion to the substrate, a (meth)acryloyl group is preferred. It should be noted that a (meth)acryloyl group refers to an acryloyl group or a methacryloyl group, and similarly, a (meth)acrylate refers to an acrylate or a methacrylate.
[0185] Regarding the liquid crystal properties displayed by the polymerizable liquid crystal compound, it can be a thermotropic liquid crystal or a lyotropic liquid crystal, but from the perspective of being able to perform precise film thickness control, a thermotropic liquid crystal is preferred. In addition, as a phase-ordered structure in a thermotropic liquid crystal, it can be a nematic liquid crystal or a smectic liquid crystal. The polymerizable liquid crystal compound can be used alone or in combination of two or more.
[0186] As the polymerizable liquid crystal compound, there can be cited a polymerizable liquid crystal compound that generally shows positive wavelength dispersion and a polymerizable liquid crystal compound that shows reverse wavelength dispersion. Only one polymerizable liquid crystal compound can be used, or two polymerizable liquid crystal compounds can be mixed and used. In a display device assembled with the obtained laminate, from the viewpoint of large suppression effect of oblique reflection hue during black display, it is preferred to include a polymerizable liquid crystal compound that shows reverse wavelength dispersion. As the polymerizable liquid crystal compound, only one can be used, or two or more can be used in combination.
[0187] As the polymerizable liquid crystal compound showing reverse wavelength dispersion, a compound having the following characteristics (A) to (D) is preferred.
[0188] (A) is a compound that can form a nematic phase or a smectic phase.
[0189] (B) The polymerizable liquid crystal compound has π electrons in the long-axis direction (a).
[0190] (C) It has π electrons in a direction intersecting the long axis direction (a) (intersecting direction (b)).
[0191] (D) The π electron density in the long axis direction (a) of the polymerizable liquid crystal compound is defined by the following formula (i), where the total number of π electrons present in the long axis direction (a) is N(πa) and the total molecular weight present in the long axis direction is N(Aa):
[0192] D(πa)=N(πa) / N(Aa)(i), and,
[0193] The total number of π electrons present in the cross direction (b) is denoted as N(πb), and the total number of molecular weights present in the cross direction (b) is denoted as N(Ab), and the π electron density in the cross direction (b) of the polymerizable liquid crystal compound is defined by the following formula (ii):
[0194] D(πb)=N(πb) / N(Ab) (ii)
[0195] The relationship of existence (iii) is:
[0196] 0≤〔D(πa) / D(πb)〕<1 (iii)
[0197] [That is, the π electron density in the cross direction (b) is greater than the π electron density in the long axis direction (a)].
[0198] In addition, as described above, the polymerizable liquid crystal compound having π electrons in the long axis and in the direction intersecting therewith forms, for example, a T-shaped structure.
[0199] In the above-mentioned features (A) to (D), the major axis direction (a) and the number of π electrons N are defined as follows.
[0200] The major axis direction (a) refers to the major axis direction of the rod, for example, in the case of a compound having a rod-like structure.
[0201] The number of π electrons N(πa) present in the major axis direction (a) does not include π electrons that disappear due to the polymerization reaction.
[0202] The number of π electrons N(πa) present in the long axis direction (a) is the total number of π electrons on the long axis and π electrons conjugated thereto, for example, including the number of π electrons present in the ring that exists in the long axis direction (a) and satisfies the Huckel rule.
[0203] The number of π electrons N(πb) present in the crossing direction (b) does not include π electrons that disappear due to the polymerization reaction.
[0204] The polymerizable liquid crystal compound satisfying the above conditions has a mesostructure in the long-axis direction, and exhibits a liquid crystal phase (nematic phase, smectic phase) due to the mesostructure.
[0205] By applying a polymerizable liquid crystal compound satisfying the above (A) to (D) on a film (layer) forming a liquid crystal cured film and heating it to a temperature above the phase transition temperature, a nematic phase or a smectic phase can be formed. The nematic phase or smectic phase formed by the orientation of the polymerizable liquid crystal compound is usually oriented in a manner that the long axis directions of the polymerizable liquid crystal compound are parallel to each other, and the long axis direction becomes the orientation direction of the nematic phase. If such a polymerizable liquid crystal compound is made into a film and polymerized in a nematic phase or a smectic phase, a polymer film formed by polymerizing in a state oriented along the long axis direction (a) can be formed. The polymer film absorbs ultraviolet rays by π electrons in the long axis direction (a) and π electrons in the cross direction (b). Among them, the absorption maximum wavelength of ultraviolet rays absorbed by the π electrons in the cross direction (b) is recorded as λbmax. λbmax is usually 300nm to 400nm. The density of π electrons satisfies the above formula (iii), and the density of π electrons in the cross direction (b) is greater than that in the long axis direction (a), so that the absorption of linearly polarized ultraviolet light (wavelength λbmax) having a vibration plane in the cross direction (b) is greater than that of linearly polarized ultraviolet light (wavelength λbmax) having a vibration plane in the long axis direction (a). The ratio (absorbance in the cross direction (b) of linearly polarized ultraviolet light / absorbance in the long axis direction (a)) is, for example, greater than 1.0, preferably greater than 1.2, and usually 30 or less, for example, 10 or less.
[0206] The polymerizable liquid crystal compound having the above-mentioned characteristics usually shows reverse wavelength dispersion. Specifically, for example, there can be mentioned a compound represented by the following formula (X).
[0207]
[0208] In formula (X), Ar represents a divalent group containing an aromatic group which may have a substituent. The aromatic group refers to a group having a π electron number of [4n+2] in the ring structure according to the Huckel rule, for example, an Ar group such as (Ar-1) to (Ar-23) described later may have two or more Ar groups as exemplified by divalent linking groups. Wherein n represents an integer. In the case where a ring structure is formed by containing heteroatoms such as -N= and -S-, the case where the non-covalent electron pairs on these heteroatoms satisfy the Huckel rule and thus have aromaticity is also included. It is preferred that at least one of a nitrogen atom, an oxygen atom, and a sulfur atom is contained in the aromatic group. The aromatic group contained in the divalent group Ar may be one or more. In the case where the aromatic group is one, the divalent group Ar may be a divalent aromatic group which may have a substituent. When the divalent group Ar contains two or more aromatic groups, the two or more aromatic groups may be bonded to each other via a single bond, a divalent bonding group such as -CO-O-, or -O-.
[0209] G 1 and G 2 Each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. The hydrogen atoms contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group or a nitro group, and the carbon atoms constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by an oxygen atom, a sulfur atom or a nitrogen atom.
[0210] L 1 , L 2 , B 1 and B 2 Each is independently a single bond or a divalent linking group.
[0211] k and l each independently represent an integer from 0 to 3, and satisfy the relationship 1≤k+1. In the case of 2≤k+1, B 1 and B 2 , G 1 and G 2 Each may be the same as or different from each other.
[0212] E 1 and E 2Each independently represents an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms. In addition, the hydrogen atoms contained in the alkanediyl group may be substituted with halogen atoms, and -CH2- contained in the alkanediyl group may be replaced with -O-, -S-, -SiH2-, or -C(=O)-.
[0213] P 1 and P 2 Each independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.
[0214] G 1 and G 2 Each independently preferably is a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms. More preferably, it is a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group. Especially preferably, it is an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group.
[0215] In addition, it is preferred that there are multiple G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group, and more preferably 1 or L 2 Bonded G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group.
[0216] L 1 and L 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -、-R a3 COOR a4 -、-R a5 OCOR a6 -、R a7 OC=OOR a8 -、-N=N-、-CR c =CR d -, or C≡C-. Among them, R a1 ~R a8 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms, and R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom.1 and L 2 Each independently is more preferably a single bond, -OR a2-1 -、-CH2-、-CH2CH2-、-COOR a4-1 -, or OCOR a6-1 -. Among them, R a2-1 , R a4-1 , R a6-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and L 2 Each independently is further preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or OCO-.
[0217] B 1 and B 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -、-R a11 COOR a12 -、-R a13 OCOR a14 -, or R a15 OC=OOR a16 -. Among them, R a9 ~R a16 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1 and B 2 Each independently is more preferably a single bond, -OR a10-1 -、-CH2-、-CH2CH2-、-COOR a12 -1 -, or OCOR a14-1 -. Among them, R a10-1 , R a12-1 , R a14-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and B 2 Each independently is further preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or OCOCH2CH2-.
[0218] From the viewpoint of exhibiting reverse wavelength dispersion, k and l are preferably in the range of 2≤k+l≤6, k+l=4 is preferred, and k=2 and l=2 are more preferred. k=2 and l=2 are preferred because a symmetrical structure is obtained.
[0219] As P 1 or P 2The polymerizable group represented by , includes epoxy, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxirane, etc. Among them, acryloyloxy, methacryloyloxy, vinyl and vinyloxy are preferred, and acryloyloxy and methacryloyloxy are more preferred.
[0220] Ar preferably has at least one selected from an aromatic hydrocarbon ring that may have a substituent, an aromatic heterocycle that may have a substituent, and an electron-withdrawing group. As the aromatic hydrocarbon ring, for example, benzene ring, naphthalene ring, anthracene ring, etc. can be cited, preferably benzene ring, naphthalene ring. As the aromatic heterocycle, furan ring, benzofuran ring, pyrrole ring, indole ring, thiophene ring, benzothiophene ring, pyridine ring, pyrazine ring, pyrimidine ring, triazole ring, triazine ring, pyrroline ring, imidazole ring, pyrazole ring, thiazole ring, benzothiazole ring, thienothiazole ring, oxazole ring, benzoxazole ring, and phenanthroline ring, etc. can be cited. Among them, preferably have thiazole ring, benzothiazole ring or benzofuran ring, further preferably have benzothiazolyl. In addition, when Ar contains a nitrogen atom, the nitrogen atom preferably has π electrons.
[0221] In formula (X), the total number of π electrons contained in the divalent aromatic group represented by Ar is N π It is preferably 8 or more, more preferably 10 or more, further preferably 14 or more, and particularly preferably 16 or more. It is preferably 30 or less, more preferably 26 or less, and further preferably 24 or less.
[0222] Examples of the aromatic group represented by Ar include the following groups.
[0223]
[0224] In the formulas (Ar-1) to (Ar-23), the symbol * represents a connecting portion, and Z 0 , Z 1 and Z 2 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms. 0 , Z 1 and Z 2 A polymerizable group may be contained.
[0225] Q 1and Q 2 Each independently represents -CR 2’ R 3’ -、-S-、-NH-、-NR 2’ -, -CO- or O-, R 2’ and R 3’ Each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0226] J 1 and J 2 Each independently represents a carbon atom or a nitrogen atom.
[0227] Y 1 , Y 2 and Y 3 Each independently represents an aromatic hydrocarbon group or an aromatic heterocyclic group which may be substituted.
[0228] W 1 and W 2 Each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom, and m represents an integer of 0-6.
[0229] As Y 1 , Y 2 and Y 3 The aromatic hydrocarbon group in the group includes aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as phenyl, naphthyl, anthracenyl, phenanthrenyl, and biphenyl, preferably phenyl and naphthyl, and more preferably phenyl. The aromatic heterocyclic group includes aromatic heterocyclic groups having 4 to 20 carbon atoms, such as furanyl, pyrrolyl, thienyl, pyridyl, thiazolyl, and benzothiazolyl, which contain at least one hetero atom such as a nitrogen atom, an oxygen atom, or a sulfur atom, preferably furanyl, thienyl, pyridyl, thiazolyl, and benzothiazolyl.
[0230] Y 1 , Y 2 and Y 3 Each independently may be a substituted polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring collection. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring collection.
[0231] Z 0 , Z 1 and Z 2 Each of Z is independently preferably a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms. 0 More preferably, a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group. 1 and Z 2More preferably, Z is a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, or a cyano group. 0 , Z 1 and Z 2 A polymerizable group may be contained.
[0232] Q 1 and Q 2 Preferred are -NH-, -S-, -NR 2’ -、-O-,R 2’ A hydrogen atom is preferred, and among them, -S-, -O-, and -NH- are particularly preferred.
[0233] Among formulae (Ar-1) to (Ar-23), formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.
[0234] In the formulas (Ar-16) to (Ar-23), Y 1 The nitrogen atom and Z that can be bonded to it 0 Together, they form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include the aromatic heterocyclic rings that Ar may have and are described above, for example, a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, a pyrrolidine ring, etc. The aromatic heterocyclic group may have a substituent. In addition, Y 1 The nitrogen atom and Z that can be bonded to it 0 Together, they form the aforementioned optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group, for example, a benzofuran ring, a benzothiazole ring, a benzoxazole ring, and the like.
[0235] In addition, in the present invention, as a polymerizable liquid crystal compound for forming a vertically aligned liquid crystal cured film, for example, a compound containing a group represented by the following formula (Y) (hereinafter also referred to as "polymerizable liquid crystal compound (Y)") can be used. The polymerizable liquid crystal compound (Y) generally tends to show positive wavelength dispersion. The polymerizable liquid crystal compound can be used alone or in combination of two or more.
[0236] P11-B11-E11-B12-A11-B13- (Y)
[0237] [In formula (Y), P11 represents a polymerizable group.
[0238] A11 represents a divalent alicyclic hydrocarbon group or a divalent aromatic hydrocarbon group.
[0239] B11 represents -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, -CO-NR 16 -、-NR 16-CO-, -CO-, -CS- or a single bond. 16 It represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
[0240] B12 and B13 each independently represent -C≡C-, -CH=CH-, -CH2-CH2-, -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-, -OC(=O)-O-, -CH=N-, -N=CH-, -N=N-, -C(=O)-NR 16 -、-NR 16 -C(=O)-, -OCH2-, -OCF2-, -CH2O-, -CF2O-, -CH=CH-C(=O)-O-, -OC(=O)-CH=CH-, -H, -C≡N or a single bond.
[0241] E11 represents an alkanediyl group having 1 to 12 carbon atoms, wherein the hydrogen atoms contained in the alkanediyl group may be substituted by an alkoxy group having 1 to 5 carbon atoms, and the hydrogen atoms contained in the alkoxy group may be substituted by a halogen atom. In addition, -CH2- constituting the alkanediyl group may be replaced by -O- or -CO-.]
[0242] The number of carbon atoms in the aromatic hydrocarbon group and alicyclic hydrocarbon group represented by A11 is preferably in the range of 3 to 18, more preferably in the range of 5 to 12, and particularly preferably 5 or 6. The hydrogen atoms contained in the divalent alicyclic hydrocarbon group and divalent aromatic hydrocarbon group represented by A11 may be substituted by a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a cyano group, or a nitro group, and the hydrogen atoms contained in the alkyl group having 1 to 6 carbon atoms and the alkoxy group having 1 to 6 carbon atoms may be substituted by a fluorine atom. As A11, cyclohexane-1,4-diyl and 1,4-phenylene are preferred.
[0243] E11 is preferably a linear alkanediyl group having 1 to 12 carbon atoms. -CH2- constituting the alkanediyl group may be replaced by -O-.
[0244] Specifically, there can be mentioned straight-chain alkanediyl groups having 1 to 12 carbon atoms, such as methylene, ethylene, propane-1,3-diyl, butane-1,4-diyl, pentane-1,5-diyl, hexane-1,6-diyl, heptane-1,7-diyl, octane-1,8-diyl, nonane-1,9-diyl, decane-1,10-diyl, undecane-1,11-diyl and dodecane-1,12-diyl; -CH2-CH2-O-CH2-CH2-, -CH2-CH2-O-CH2-CH2-O-CH2-CH2- and -CH2-CH2-O-CH2-CH2-O-CH2-CH2-O-CH2-CH2-, etc.
[0245] As B11, -O-, -S-, -CO-O-, and -O-CO- are preferred, and among them, -CO-O- is more preferred.
[0246] As B12 and B13, each independently, -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-, and -OC(=O)-O- are preferred, and among them, -O- or -OC(=O)-O- is more preferred.
[0247] As the polymerizable group represented by P11, from the perspective of high polymerization reactivity, especially photopolymerization reactivity, it is preferably a free radical polymerizable group or a cationic polymerizable group. From the perspective of easy operation and easy manufacture of the liquid crystal compound itself, the polymerizable group is preferably a group represented by the following formula (P-11) to (P-15).
[0248]
[0249] [In formulas (P-11) to (P-15),
[0250] R 17 ~R 21 Each independently represents an alkyl group having 1 to 6 carbon atoms or a hydrogen atom.]
[0251] Specific examples of the groups represented by formula (P-11) to formula (P-15) include groups represented by the following formula (P-16) to formula (P-20).
[0252]
[0253] P11 is preferably a group represented by formula (P-14) to formula (P-20), and more preferably a vinyl group, a p-stilbene group, an epoxy group, or an oxetanyl group.
[0254] The group represented by P11-B11- is more preferably an acryloyloxy group or a methacryloyloxy group.
[0255] Examples of the polymerizable liquid crystal compound (Y) include compounds represented by formula (I), formula (II), formula (III), formula (IV), formula (V) or formula (VI).
[0256] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-B16-E12-B17-P12(I)
[0257] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-F11(II)
[0258] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-E12-B17-P12(III)
[0259] P11-B11-E11-B12-A11-B13-A12-B14-A13-F11(IV)
[0260] P11-B11-E11-B12-A11-B13-A12-B14-E12-B17-P12(V)
[0261] P11-B11-E11-B12-A11-B13-A12-F11(VI)
[0262] (Where,
[0263] A11, B11 to B13 and P11 have the same meanings as in the above formula (A),
[0264] A12 to A14 each independently have the same meaning as A11, B14 to B16 each independently have the same meaning as B12, B17 has the same meaning as B11, E12 has the same meaning as E11, and P12 has the same meaning as P11.
[0265] F11 represents a hydrogen atom, an alkyl group having 1 to 13 carbon atoms, an alkoxy group having 1 to 13 carbon atoms, a cyano group, a nitro group, a trifluoromethyl group, a dimethylamino group, a hydroxyl group, a hydroxymethyl group, a formyl group, a sulfo group (-SO3H), a carboxyl group, an alkoxycarbonyl group having 1 to 10 carbon atoms, or a halogen atom, and -CH2- constituting the alkyl group and the alkoxy group may be replaced by -O-.
[0266] Specific examples of polymerizable liquid crystal compounds (Y) include compounds having polymerizable groups recorded in "3.8.6 Network (Completely Cross-linked Type)" and "6.5.1 Liquid Crystal Materials b. Polymerizable Nematic Liquid Crystal Materials" of Liquid Crystal Handbook (edited by Liquid Crystal Handbook Editorial Committee, published by Maruzen Co., Ltd. on October 30, 2000), and polymerizable liquid crystals recorded in Japanese Patent Gazette Nos. 2010-31223, 2010-270108, 2011-6360 and 2011-207765.
[0267] As specific examples of polymerizable liquid crystal compounds (Y), compounds represented by the following formulas (I-1) to (I-4), (II-1) to (II-4), (III-1) to (III-26), (IV-1) to (IV-26), (V-1) to (V-2) and (VI-1) to (VI-6) can be cited. It should be noted that in the following formula, k1 and k2 each independently represent an integer of 2 to 12. These polymerizable liquid crystal compounds (Y) are preferred from the perspective of ease of synthesis or ease of acquisition.
[0268]
[0269]
[0270]
[0271]
[0272]
[0273]
[0274]
[0275] With respect to the content of the polymerizable liquid crystal compound in the vertically oriented liquid crystal curing film forming composition for forming a vertically oriented liquid crystal curing film, relative to 100 parts by mass of the solid content of the vertically oriented liquid crystal curing film forming composition, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and further preferably 90 to 95 parts by mass. When the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the perspective of the orientation of the obtained liquid crystal curing film. It should be noted that in the present invention, the solid content of the polymerizable liquid crystal composition refers to all components after removing volatile components such as organic solvents from the polymerizable liquid crystal composition. In addition, when the polymerizable liquid crystal composition contains two or more polymerizable liquid crystal compounds, it is preferred that the total content of all polymerizable liquid crystal compounds contained in the polymerizable liquid crystal composition is within the above range.
[0276] The adhesion between the substrate and the vertically aligned liquid crystal cured film in the laminate of the present invention can be improved, for example, by forming a vertically aligned liquid crystal cured film containing the following compound (hereinafter also referred to as "pre-reaction compound") on a substrate having a hydroxyl group or a carboxyl group on the surface, wherein the compound has a functional group capable of reacting with the hydroxyl group or the carboxyl group and a (meth) acryloyl group in the molecule. By adjusting the surface treatment state of the above-mentioned substrate, the type and content of the pre-reaction compound contained in the vertically aligned liquid crystal cured film, etc., the substrate peeling force P of the laminate can be controlled.
[0277] Therefore, the composition for forming the vertical alignment liquid crystal solidification film of the laminate of the present invention is preferably included in the compound having a functional group and (meth) acryloyl group that can react with a hydroxyl or carboxyl group in the molecule. If a pre-reaction compound is included, when forming a vertical alignment liquid crystal solidification film, the (meth) acryloyl group possessed by the pre-reaction compound reacts with the polymerizable group (especially (meth) acryloyl group) possessed by the polymerizable liquid crystal compound. In addition, the functional group that can react with a hydroxyl or carboxyl group possessed by the pre-reaction compound also reacts with the hydroxyl and / or carboxyl group present on the substrate surface. By the above two reactions, through the pre-reaction compound, a cross-linked structure and a network structure are formed between the substrate and the main component constituting the vertical alignment liquid crystal solidification film, that is, the polymerizable liquid crystal compound, so that the adhesion of the vertical alignment liquid crystal solidification film to the substrate can be improved.
[0278] As the functional group that can react with hydroxyl or carboxyl group possessed by the pre-reaction compound, as long as it is a functional group that can easily react with hydroxyl or carboxyl group, it is not particularly limited. For example, isocyanate group, epoxy group, oxetanyl group, silanol group, alkoxysilyl group, carboxyl group, hydroxyl group, amino group, acyl chloride group, hydroxysilyl group etc. can be cited. The pre-reaction compound has at least one functional group that can react with hydroxyl or carboxyl group in the molecule, and in the case of comprising more than 2 above-mentioned functional groups, these functional groups can be the same or different. Among them, from the viewpoint of being relatively reactive and easy to operate, it is preferred to be selected from at least one of the group consisting of isocyanate group, epoxy group, oxetanyl group, silanol group, alkoxysilyl group and hydroxysilyl group, more preferably selected from at least one of the group consisting of alkoxysilyl group and hydroxysilyl group.
[0279] The molecular weight of the pre-reaction compound is preferably less than 10000, more preferably less than 5000, and further preferably less than 3000. When the molecular weight of the pre-reaction compound is below the above upper limit, it is not easy to form the orientation disorder of the polymerizable liquid crystal compound of the vertical alignment film, and it is possible to improve the adhesion with the substrate while ensuring the high orientation accuracy of the polymerizable liquid crystal compound. On the other hand, the more the number of covalent bonds between the functional group capable of reacting with a hydroxyl or carboxyl group in the pre-reaction compound and the (meth) acryloyl group, the easier it is to improve the adhesion of the substrate to the vertical alignment liquid crystal cured film, therefore, the molecular weight of the pre-reaction compound is preferably more than 50, more preferably more than 100, and more preferably more than 300.
[0280] In the present invention, as a pre-reaction compound, a compound having a functional group capable of reacting with a hydroxyl group or a carboxyl group and a (meth) acryloyl group in the molecule can be added to prepare a vertical alignment liquid crystal curing film forming composition. In addition, the pre-reaction compound can be prepared while preparing the vertical alignment liquid crystal curing film forming composition. As the pre-reaction compound, only one type can be used, or two or more types can be used in combination.
[0281] When preparing a pre-reaction compound while preparing a composition for forming a vertically aligned liquid crystal curing film, it is preferred to use a chemical reaction that is also easy to react quantitatively at room temperature to form a pre-reaction compound, such as a chemical reaction that reacts a hydroxyl group with an isocyanate group, or an amino group with an isocyanate group to form a carbamate bond or a urea bond. For example, in a composition for forming a vertically aligned liquid crystal curing film, or in its preparation process, a first compound having a functional group capable of reacting with a hydroxyl group or a carboxyl group and an amino group, and a second compound having a (meth) acryloyl group and an isocyanate group are added, and a pre-reaction compound having a functional group capable of reacting with a hydroxyl group or a carboxyl group from the first compound and a (meth) acryloyl group from the second compound can be obtained. The compound as a material for forming the pre-reaction compound can be added to the composition for forming a vertically aligned liquid crystal curing film after being mixed in an appropriate solvent, etc. as needed, or it can be directly mixed with other components constituting the composition for forming a vertically aligned liquid crystal curing film.
[0282] When there is a tendency that the greater the number of covalent bonds between the functional group capable of reacting with a hydroxyl group or a carboxyl group in the pre-reaction compound and the (meth)acryloyl group, the easier it is to improve the adhesion between the substrate and the vertically aligned liquid crystal cured film. Thus, the above-mentioned number of covalent bonds can be adjusted, and the adhesion between the substrate and the vertically aligned liquid crystal cured film can be easily controlled. From this aspect, in the present invention, the pre-reaction compound is more preferably produced by chemical reaction in the composition for forming a vertically aligned liquid crystal cured film or in its production process.
[0283] As compounds suitable for preparing such pre-reaction compounds, for example, compounds having an alkoxysilyl group and an amino group as the above-mentioned first compound [for example, KBE-903, KBM-602, KBM-903 (all of which are manufactured by Shin-Etsu Chemical Co., Ltd.)], etc. can be cited. In addition, compounds having a (meth)acryloyl group and an isocyanate group as the above-mentioned second compound [for example, Karenz MOI-EG, Karenz MOI, Karenz AOI, Karenz BEI (all of which are manufactured by Showa Denko K.K.)], etc. can be cited. By appropriately combining these compounds, a pre-reaction compound can be obtained. The mixing ratio of each compound used to prepare the pre-reaction compound can be appropriately selected based on the structure of the compound used and the chemical reaction utilized.
[0284] Relative to 100 parts by mass of the polymerizable liquid crystal compound contained in the composition for forming vertically aligned liquid crystal curing film, the content of the pre-reaction compound in the composition for forming vertically aligned liquid crystal curing film is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, and further preferably 0.3 parts by mass or more. When the content of the pre-reaction compound is above the above lower limit, the functional group that can react with a hydroxyl or carboxyl group, the (meth) acryloyl group possessed by the pre-reaction compound reacts fully with the hydroxyl or carboxyl group present on the surface of the substrate, and the polymerizable group (especially (meth) acryloyl group) possessed by the polymerizable liquid crystal compound, and the adhesion of the substrate to the vertically aligned liquid crystal curing film can be improved. In addition, relative to 100 parts by mass of the polymerizable liquid crystal compound contained in the composition for forming vertically aligned liquid crystal curing film, the content of the pre-reaction compound is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and further preferably 5 parts by mass or less. When the content of the pre-reaction compound is below the above upper limit, the substrate and the vertically aligned liquid crystal curing film are laminated with appropriate adhesion, and therefore, the substrate can be cleanly peeled off from the laminate with a small force. In addition, the adhesiveness can be controlled while ensuring high alignment accuracy of the polymerizable liquid crystal compound constituting the vertically aligned liquid crystal cured film.
[0285] In a preferred embodiment of the present invention, hydroxyl groups and / or carboxyl groups are present on the surface of the substrate for forming a vertically oriented liquid crystal curing film, and the composition for forming a vertically oriented liquid crystal curing film comprises the following components: a compound having a functional group and a (meth)acryloyl group that can react with the hydroxyl groups and / or carboxyl groups present on the surface of the substrate; and a polymerizable liquid crystal compound having a (meth)acryloyl group as a polymerizable group and an ionic compound formed by non-metallic atoms. When the substrate surface and the composition for forming a vertically oriented liquid crystal curing film have the above-mentioned structure, a vertically oriented liquid crystal curing film can be formed without forming a vertically oriented film on the substrate, and the adhesion between the substrate and the vertically oriented liquid crystal curing film can be easily controlled, so that the most suitable adhesion between the substrate and the vertically oriented liquid crystal curing film and the substrate peeling force can be achieved. It should be noted that the hydroxyl groups and carboxyl groups on the surface of the substrate can be provided by a known surface treatment method described later.
[0286] In the present invention, the vertically aligned liquid crystal curing film preferably contains at least one polymerizable non-liquid crystal compound having two or more (meth) acryloyl groups (hereinafter, also referred to as "multifunctional (meth) acrylate compound"). By containing the multifunctional (meth) acrylate compound, the (meth) acryloyl group of the multifunctional (meth) acrylate compound and the polymerizable group (especially (meth) acryloyl group) of the polymerizable liquid crystal compound in the vertically aligned liquid crystal curing film can form a cross-linked structure. Thus, the network structure formed by the above-mentioned pre-reaction compound and the polymerizable liquid crystal compound can be enhanced, and the adhesion between the substrate and the vertically aligned liquid crystal curing film can be further improved.
[0287] The multifunctional (meth)acrylate compound refers to a compound having two or more (meth)acryloyl groups in the molecule, and examples thereof include a bifunctional (meth)acrylate monomer having two (meth)acryloyl groups in the molecule, a trifunctional or higher (meth)acrylate monomer having three or more (meth)acryloyl groups in the molecule, etc. In the present invention, the vertically aligned liquid crystal cured film may contain one or two or more multifunctional (meth)acrylate compounds, and when containing two or more multifunctional (meth)acrylate compounds, they may be the same or different.
[0288] Examples of the bifunctional (meth)acrylate monomer include alkylene glycol di(meth)acrylates such as ethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate; diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and polyethylene glycol di(meth)acrylate. Polyoxyalkylene glycol di(meth)acrylates such as polyol di(meth)acrylate, polypropylene glycol di(meth)acrylate and polytetramethylene glycol di(meth)acrylate; di(meth)acrylates of halogen-substituted alkylene glycols such as tetrafluoroethylene glycol di(meth)acrylate; di(meth)acrylates of aliphatic polyols such as trimethylolpropane di(meth)acrylate, ditrimethylolpropane di(meth)acrylate and pentaerythritol di(meth)acrylate; hydrogenated dicyclopentadienyl di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, etc. Di(meth)acrylate of hydrogenated dicyclopentadiene or tricyclodecanediol; di(meth)acrylate of dioxanediol or dioxanediol such as 1,3-dioxane-2,5-diol di(meth)acrylate [alias: dioxanediol di(meth)acrylate]; di(meth)acrylate of bisphenol A or bisphenol F ethylene oxide adduct such as bisphenol A ethylene oxide adduct diacrylate and bisphenol F ethylene oxide adduct diacrylate; acrylic acid adduct of bisphenol A diglycidyl ether and acrylic acid adduct of bisphenol F diglycidyl ether Adducts such as epoxy di(meth)acrylate of bisphenol A or bisphenol F; silicone di(meth)acrylate; di(meth)acrylate of hydroxypivalic acid neopentyl glycol ester; 2,2-bis[4-(meth)acryloyloxyethoxyethoxyphenyl]propane; 2,2-bis[4-(meth)acryloyloxyethoxyethoxycyclohexyl]propane; di(meth)acrylate of 2-(2-hydroxy-1,1-dimethylethyl)-5-ethyl-5-hydroxymethyl-1,3-dioxane]; tris(hydroxyethyl)isocyanurate di(meth)acrylate, etc.
[0289] The trifunctional (meth)acrylate monomer is a monomer having three (meth)acryloyl groups in the molecule, and examples thereof include glycerol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, a reaction product of pentaerythritol tri(meth)acrylate and anhydride, caprolactone-modified trimethylolpropane tri(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, ethylene oxide-modified tri(meth)acrylate, and di(meth)acrylate. Methylpropane tri(meth)acrylate, ethylene oxide modified pentaerythritol tri(meth)acrylate, propylene oxide modified trimethylolpropane tri(meth)acrylate, propylene oxide modified pentaerythritol tri(meth)acrylate, isocyanurate tri(meth)acrylate, a reaction product of caprolactone modified pentaerythritol tri(meth)acrylate and anhydride, a reaction product of ethylene oxide modified pentaerythritol tri(meth)acrylate and anhydride, a reaction product of propylene oxide modified pentaerythritol tri(meth)acrylate and anhydride, and the like.
[0290] The tetrafunctional (meth)acrylate monomer is a monomer having four (meth)acryloyl groups in the molecule, and examples thereof include ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, tripentaerythritol tetra(meth)acrylate, caprolactone-modified pentaerythritol tetra(meth)acrylate, caprolactone-modified tripentaerythritol tetra(meth)acrylate, ethylene oxide-modified pentaerythritol tetra(meth)acrylate, ethylene oxide-modified tripentaerythritol tetra(meth)acrylate, propylene oxide-modified pentaerythritol tetra(meth)acrylate, and propylene oxide-modified tripentaerythritol tetra(meth)acrylate.
[0291] Examples of the pentafunctional (meth)acrylate monomer include dipentaerythritol penta(meth)acrylate, tripentaerythritol penta(meth)acrylate, a reaction product of dipentaerythritol penta(meth)acrylate and an acid anhydride, caprolactone-modified dipentaerythritol penta(meth)acrylate, caprolactone-modified tripentaerythritol penta(meth)acrylate, ethylene oxide-modified dipentaerythritol penta(meth)acrylate, ethylene oxide-modified tripentaerythritol penta(meth)acrylate, propylene oxide-modified dipentaerythritol penta(meth)acrylate, propylene oxide-modified tripentaerythritol penta(meth)acrylate, a reaction product of caprolactone-modified dipentaerythritol penta(meth)acrylate and an acid anhydride, a reaction product of ethylene oxide-modified dipentaerythritol penta(meth)acrylate and an acid anhydride, and a reaction product of propylene oxide-modified dipentaerythritol penta(meth)acrylate and an acid anhydride.
[0292] Examples of the hexafunctional (meth)acrylate monomer include dipentaerythritol hexa(meth)acrylate, tripentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, caprolactone-modified tripentaerythritol hexa(meth)acrylate, ethylene oxide-modified dipentaerythritol hexa(meth)acrylate, ethylene oxide-modified tripentaerythritol hexa(meth)acrylate, propylene oxide-modified dipentaerythritol hexa(meth)acrylate, and propylene oxide-modified tripentaerythritol hexa(meth)acrylate.
[0293] Examples of the heptafunctional (meth)acrylate monomer include tripentaerythritol hepta(meth)acrylate, a reaction product of tripentaerythritol hepta(meth)acrylate and an acid anhydride, caprolactone-modified tripentaerythritol hepta(meth)acrylate, a reaction product of caprolactone-modified tripentaerythritol hepta(meth)acrylate and an acid anhydride, ethylene oxide-modified tripentaerythritol hepta(meth)acrylate, a reaction product of ethylene oxide-modified tripentaerythritol hepta(meth)acrylate and an acid anhydride, propylene oxide-modified tripentaerythritol hepta(meth)acrylate, a reaction product of propylene oxide-modified tripentaerythritol hepta(meth)acrylate and an acid anhydride, and the like.
[0294] The octafunctional (meth)acrylate monomer is a monomer having 8 (meth)acryloyl groups in the molecule, and examples thereof include tripentaerythritol octa(meth)acrylate, caprolactone-modified tripentaerythritol octa(meth)acrylate, ethylene oxide-modified tripentaerythritol octa(meth)acrylate, and propylene oxide-modified tripentaerythritol octa(meth)acrylate.
[0295] The number of (meth)acryloyl groups in the multifunctional (meth)acrylate compound is preferably 2 to 6. When the number of (meth)acryloyl groups in the multifunctional (meth)acrylate compound is within the above range, a cross-linking structure is formed with a polymerizable liquid crystal compound constituting the vertically aligned liquid crystal cured film (especially a polymerizable liquid crystal compound having a (meth)acryloyl group as a polymerizable group) to increase the cross-linking density, thereby increasing the network structure constructed between the substrate and the vertically aligned liquid crystal cured film via the pre-reacted compound, and improving the adhesion between the substrate and the vertically aligned liquid crystal cured film.
[0296] The crosslinking density of the vertically aligned liquid crystal cured film can be adjusted by controlling the molecular weight and the number of crosslinking points of the multifunctional (meth)acrylate compound. In more detail, the smaller the molecular weight between the crosslinking points, the higher the crosslinking density. In addition, the more the number of crosslinking points, the denser the crosslinking density, and the better the adhesion.
[0297] The molecular weight of the multifunctional (meth) acrylate compound is preferably 1000 or less, more preferably 900 or less, and further preferably 850 or less. When the molecular weight of the multifunctional (meth) acrylate is below the above upper limit, it is not easy to disturb the orientation of the polymerizable liquid crystal compound forming the vertical alignment film, and it is possible to improve the adhesion with the substrate while ensuring the high orientation accuracy of the polymerizable liquid crystal compound. The lower limit of the molecular weight of the multifunctional (meth) acrylate compound is not particularly limited, and is usually 100 or more, preferably 200 or more.
[0298] The content of the multifunctional (meth) acrylate compound in the composition for forming a vertically aligned liquid crystal curing film is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, further preferably 0.3 parts by mass or more, preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and further preferably 5 parts by mass or less, relative to 100 parts by mass of the polymerizable liquid crystal compound contained in the composition for forming a vertically aligned liquid crystal curing film. When the content of the multifunctional (meth) acrylate compound is within the above range, it is not easy to disturb the orientation of the polymerizable liquid crystal compound forming the vertically aligned film, and it is possible to achieve the most suitable adhesion and substrate peeling force between the substrate and the vertically aligned liquid crystal curing film while ensuring the high orientation accuracy of the polymerizable liquid crystal compound.
[0299] In a preferred embodiment of the present invention, hydroxyl groups and / or carboxyl groups are present on the surface of the substrate on which the vertical alignment liquid crystal curing film is formed, and the composition for forming the vertical alignment liquid crystal curing film comprises the following components: a compound having a functional group and a (meth)acryloyl group that can react with the hydroxyl groups and / or carboxyl groups present on the surface of the substrate, and a multifunctional (meth)acrylate compound, and a polymerizable liquid crystal compound having a (meth)acryloyl group as a polymerizable group, and an ionic compound formed by non-metallic atoms. When the surface of the substrate and the composition for forming the vertical alignment liquid crystal curing film have the above-mentioned constitution, the vertical alignment liquid crystal curing film can be formed without forming a vertical alignment film on the substrate, and the adhesion between the substrate and the vertical alignment liquid crystal curing film can be easily controlled, and more appropriate adhesion between the substrate and the vertical alignment liquid crystal curing film and the substrate peeling force can be achieved.
[0300] The composition for forming a vertically aligned liquid crystal cured film (polymerizable liquid crystal composition) used in the formation of a vertically aligned liquid crystal cured film may contain additives such as a solvent, a polymerization initiator, a leveling agent, an antioxidant, and a photosensitizer in addition to a vertically aligned accelerator and a polymerizable liquid crystal compound, the above-mentioned pre-reacted compound and / or a multifunctional (meth)acrylate compound. Each of these components may be used alone or in combination of two or more.
[0301] The composition for forming a vertically aligned liquid crystal solidified film is usually applied to a substrate in a state dissolved in a solvent, and therefore preferably contains a solvent. As the solvent, it is preferably a solvent that can dissolve the polymerizable liquid crystal compound, and it is also preferably a solvent that is inactive for the polymerization reaction of the polymerizable liquid crystal compound. Examples of the solvent include alcohol solvents such as water, methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, 1-methoxy-2-propanol, 2-butoxyethanol, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; alicyclic hydrocarbon solvents such as ethylcyclohexane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorinated solvents such as chloroform and chlorobenzene; amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone (NMP), and 1,3-dimethyl-2-imidazolidinone; and the like. These solvents may be used alone or in combination of two or more. Among them, alcohol solvents, ester solvents, ketone solvents, chlorine-containing solvents, amide solvents, and aromatic hydrocarbon solvents are preferred.
[0302] Relative to 100 parts by mass of the composition, the content of the solvent in the vertically aligned liquid crystal curing film forming material is preferably 50 to 98 parts by mass, more preferably 70 to 95 parts by mass. Therefore, the solid component preferably accounts for 2 to 50 parts by mass in 100 parts by mass of the composition for forming a vertically aligned liquid crystal curing film. When the solid component is less than 50 parts by mass, the viscosity of the composition for forming a vertically aligned liquid crystal curing film decreases, so there is a tendency that the thickness of the film becomes roughly uniform and is not easy to produce unevenness. The above-mentioned solid component can be appropriately determined in consideration of the thickness of the liquid crystal curing film to be manufactured.
[0303] The polymerization initiator is a compound that generates reactive species by the contribution of heat or light and can initiate a polymerization reaction of a polymerizable liquid crystal compound or the like. As reactive species, there can be mentioned active species such as free radicals, cations or anions. Among them, from the viewpoint of easy control of the reaction, a photopolymerization initiator that generates free radicals by light irradiation is preferred.
[0304] Examples of the photopolymerization initiator include benzoin compounds, benzophenone compounds, benzyl ketal compounds, α-hydroxyketone compounds, α-aminoketone compounds, oxime compounds, triazine compounds, iodonium salts, and sulfonium salts. Specific examples include Irgacure (registered trademark) 907, Irgacure 184, Irgacure 651, Irgacure 819, Irgacure 250, Irgacure 369, Irgacure 379, Irgacure 127, Irgacure 2959, Irgacure 754, and Irgacure 379EG (all manufactured by BASF Japan Co., Ltd.), SEIKUOL BZ, SEIKUOL Z, and SEIKUOL BEE (all manufactured by Seiko Chemical Industries, Ltd.), kayacure BP100 (manufactured by Nippon Kayaku Co., Ltd.), kayacure UVI-6992 (manufactured by DOW), and ADEKA OPTOMER. SP-152, ADEKA OPTOMER SP-170, ADEKA OPTOMER N-1717, ADEKA OPTOMER N-1919, ADEKA ARKLS NCI-831, ADEKA ARKLSNCI-930 (the above are made by ADEKA Co., Ltd.), TAZ-A, TAZ-PP (the above are made by Japan Siber Hegner Co., Ltd.) and TAZ-104 (the above are made by Sanwa Chemical Co., Ltd.).
[0305] The photopolymerization initiator preferably has a maximum absorption wavelength of 300 nm to 400 nm, more preferably 300 nm to 380 nm, in order to fully utilize the energy emitted from the light source and achieve excellent productivity. Among them, α-acetophenone-based polymerization initiators and oxime-based photopolymerization initiators are preferred.
[0306] Examples of the α-acetophenone compound include 2-methyl-2-morpholino-1-(4-methylthiophenyl)-1-propanone, 2-dimethylamino-1-(4-morpholinophenyl)-2-benzyl-1-butanone, and 2-dimethylamino-1-(4-morpholinophenyl)-2-(4-methylphenylmethyl)-1-butanone. More preferred examples include 2-methyl-2-morpholino-1-(4-methylthiophenyl)-1-propanone and 2-dimethylamino-1-(4-morpholinophenyl)-2-benzyl-1-butanone. Examples of commercially available α-acetophenone compounds include Irgacure 369, 379EG, and 907 (all manufactured by BASF Japan Co., Ltd.) and SEIKUOL BEE (manufactured by Seiko Chemical Co., Ltd.).
[0307] Oxime-based photopolymerization initiators generate free radicals such as phenyl radicals and methyl radicals by irradiating light. The polymerization of the polymerizable liquid crystal compound is suitably carried out by the free radical, wherein the oxime-based photopolymerization initiator that can generate methyl radicals is preferred from the perspective of high initiation efficiency of the polymerization reaction. In addition, from the perspective of making the polymerization reaction more efficient, it is preferred to use a photopolymerization initiator that can efficiently utilize ultraviolet rays of more than 350nm. As a photopolymerization initiator that can efficiently utilize ultraviolet rays of more than 350nm, it is preferably a triazine compound or a carbazole compound containing an oxime structure, and from the perspective of sensitivity, it is more preferably a carbazole compound containing an oxime ester structure. As a carbazole compound containing an oxime structure, 1,2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyl oxime)], O-acetyl-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-1-(acetone oxime) and the like can be cited. Examples of commercially available products of oxime ester-based photopolymerization initiators include Irgacure OXE-01, Irgacure OXE-02, and Irgacure OXE-03 (all manufactured by BASF Japan Co., Ltd.), ADEKA OPTOMER N-1919, and ADEKA ARKLS NCI-831 (all manufactured by ADEKA Corporation).
[0308] The content of the photopolymerization initiator is usually 0.1 to 30 parts by mass, preferably 1 to 20 parts by mass, and more preferably 1 to 15 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound. Within the above range, the reaction of the polymerizable group proceeds sufficiently and the alignment of the polymerizable liquid crystal compound is less likely to be disturbed.
[0309] The leveling agent is an additive having a function of adjusting the fluidity of the vertically aligned liquid crystal cured film-forming composition and making the coating film obtained by applying the composition flatter, and examples thereof include silicone-based, polyacrylate-based, and perfluoroalkyl-based leveling agents.As the leveling agent, commercially available products can be used, and specific examples thereof include DC3PA, SH7PA, DC11PA, SH28PA, SH29PA, SH30PA, ST80PA, ST86PA, SH8400, SH8700, and FZ2123 (all manufactured by Dow Corning Toray Co., Ltd.), KP321, KP323, KP324, KP326, KP340, KP341, X22-161A, and KF6001 (all manufactured by Shin-Etsu Chemical Co., Ltd.), TSF400, TSF401, TSF410, TSF4300, TSF4440, TSF4445, TSF-4446, TSF4452, and TSF4460 (all manufactured by Momentive Performance Materials Japan LLC), fluorinert (registered trademark) FC-72, fluorinert FC-40, fluorinert FC-43, fluorinert FC-3283 (all manufactured by Sumitomo 3M Co., Ltd.), MEGAFACE (registered trademark) R-08, MEGAFACE R-30, MEGAFACE R-90, MEGAFACE F-410, MEGAFACE F-411, MEGAFACE F-443, MEGAFACE F-445, MEGAFACE F-470, MEGAFACE F-477, MEGAFACE F-479, MEGAFACE F-482, MEGAFACE F-483, MEGAFACE F-556 (all manufactured by DIC Corporation), EFTOP (trade name) EF301, EFTOP EF303, EFTOP EF351, EFTOP EF352 (all of the above are manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.), Surflon (registered trademark) S-381, Surflon S-382, Surflon S-383, Surflon S-393, Surflon SC-101, Surflon SC-105, KH-40, SA-100 (all of the above are manufactured by AGC Seimi Chemical Co., Ltd.), trade name E1830, trade name E5844 (manufactured by Daikin Fine Chemical Kenkyusho, KK), BM-1000, BM-1100, BYK-352, BYK-353 and BYK-361N (all trade names: manufactured by BM Chemie), etc.The leveling agent can be used alone or in combination of two or more.
[0310] The content of the leveling agent is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. When the content of the leveling agent is within the above range, it is preferred because it tends to make the polymerizable liquid crystal compound more oriented and the resulting liquid crystal cured film smoother.
[0311] By combining an antioxidant, the polymerization reaction of the polymerizable liquid crystal compound can be controlled. As an antioxidant, it can be a primary antioxidant selected from phenolic antioxidants, amine antioxidants, quinone antioxidants, and nitroso antioxidants, or it can be a secondary antioxidant selected from phosphorus antioxidants and sulfur antioxidants. In order to polymerize the polymerizable liquid crystal compound without disturbing the orientation of the polymerizable liquid crystal compound, the content of the antioxidant is generally 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound. The antioxidant can be used alone or in combination of two or more.
[0312] In addition, by using a photosensitizer, the photopolymerization initiator can be highly sensitive. As a photosensitizer, for example, xanthone such as xanthone and thioxanthone; anthracene and anthracene having a substituent such as an alkyl ether; phenothiazine; rubrene. The photosensitizer can be used alone or in combination of two or more. The content of the photosensitizer is generally 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound.
[0313] The composition for forming a vertically aligned liquid crystal curable film can be obtained by stirring the components other than the vertically aligned liquid crystal accelerator and the polymerizable liquid crystal compound, and the pre-reaction compound and / or the multifunctional (meth)acrylate compound, the solvent, the photopolymerization initiator, etc. at a predetermined temperature. It should be noted that, when the pre-reaction compound is formed in the composition for forming a vertically aligned liquid crystal curable film, for example, it can be prepared by preparing a mixture of the components required for forming the pre-reaction compound, and stirring the mixture together with the vertically aligned liquid crystal accelerator, the polymerizable liquid crystal compound, etc. at a predetermined temperature.
[0314] In the present invention, it is preferred that the vertically aligned liquid crystal cured film is oriented in a manner having a high degree of order in the vertical direction of the liquid crystal cured film. In the vertically aligned liquid crystal cured film, the polymerizable liquid crystal compound is oriented in a manner having a high degree of order, so that when the laminate including the vertically aligned liquid crystal cured film is assembled into an organic EL display device, there is a tendency that the effect of suppressing the oblique reflection hue change during black display is excellent. As an index indicating the high orientation state of the polymerizable liquid crystal compound in the vertically aligned liquid crystal cured film and the degree of the oblique optical compensation effect during black display, the vertically aligned liquid crystal cured film preferably satisfies the following formula (2).
[0315] -150nm≤RthC(550)≤-30nm (2)
[0316] In formula (2), RthC (550) represents the phase difference value in the thickness direction of the vertically aligned liquid crystal cured film at a wavelength of 550 nm. From the viewpoint of being able to further improve the oblique reflection hue during black display, the phase difference value RthC (550) in the thickness direction of the vertically aligned liquid crystal cured film is more preferably -130 nm or more, more preferably -100 nm or more, particularly preferably -90 nm or more, and more preferably -40 nm or less, and more preferably -50 nm or less.
[0317] Moreover, in one aspect of this invention, the vertically-aligned liquid crystal cured film satisfies the following formula (3).
[0318] RthC(450) / RthC(550)≤1.0 (3)
[0319] [In formula (3), RthC(450) represents the phase difference value in the film thickness direction of the vertically aligned liquid crystal cured film at a wavelength of 450 nm, and RthC(550) represents the phase difference value in the film thickness direction of the vertically aligned liquid crystal cured film at a wavelength of 550 nm.]
[0320] By satisfying the above formula (3), the decrease in the ellipticity of the laminate including the vertically aligned liquid crystal cured film on the short wavelength side can be suppressed, and the oblique reflection hue during black display can be improved. The value of RthC (450) / RthC (550) of the vertically aligned liquid crystal cured film is more preferably 0.95 or less, further preferably 0.92 or less, particularly preferably 0.9 or less, and preferably 0.7 or more, more preferably 0.75 or more, and further preferably 0.8 or more.
[0321] The phase difference value RthC(λ) in the thickness direction of the vertically aligned liquid crystal cured film can be adjusted by the thickness dC of the vertically aligned liquid crystal cured film. The in-plane phase difference value is determined by the following formula:
[0322] RthC(λ)=((nxC(λ)+nyC(λ)) / 2-nzC(λ))×dC
[0323] (Wherein, nxC(λ) represents the in-plane principal refractive index of the vertically oriented liquid crystal cured film at a wavelength of λnm, nyC(λ) represents the refractive index in the direction orthogonal to nxC(λ) in the plane at a wavelength of λnm, nzC(λ) represents the refractive index in the thickness direction of the vertically oriented liquid crystal cured film at a wavelength of λnm, and when nxC(λ)=nyC(λ), nxC(λ) can be set to the refractive index in any direction in the film plane, and dC represents the film thickness of the vertically oriented liquid crystal cured film). Therefore, in order to obtain the desired phase difference value RthC(λ) in the thickness direction, it is sufficient to adjust the three-dimensional refractive index and the film thickness dC. It should be noted that the three-dimensional refractive index depends on the molecular structure and orientation state of the aforementioned polymerizable liquid crystal compound.
[0324] As the substrate constituting the laminate of the present invention, for example, a glass substrate, a film substrate, etc. can be cited, but from the viewpoint of processability, a resin film substrate is preferred. As the resin constituting the film substrate, for example, polyolefins such as polyethylene, polypropylene, and norbornene polymers; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose esters such as cellulose triacetate, cellulose diacetate, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyethersulfone; polyetherketone; plastics such as polyphenylene sulfide and polyphenylene ether can be cited. Such a resin can be made into a substrate by a known means such as a solvent casting method and a melt extrusion method.
[0325] As the substrate, commercially available products can be used. Examples of commercially available cellulose ester substrates include cellulose ester substrates manufactured by Fuji Photo Film Co., Ltd. such as Fujitack Film; cellulose ester substrates manufactured by Konica Minolta Opto Co., Ltd. such as "KC8UX2M", "KC8UY", and "KC4UY", etc. Examples of commercially available cyclic olefin resins include cyclic olefin resins manufactured by Ticona (Germany) such as "Topas (registered trademark)"; cyclic olefin resins manufactured by JSR Corporation such as "ARTON (registered trademark)"; cyclic olefin resins manufactured by Zeon Co., Ltd. such as "ZEONOR (Registered Trademark)" and "ZEONEX (Registered Trademark)"; and cyclic olefin resins manufactured by Mitsui Chemicals, Inc. such as "Apel (Registered Trademark). Commercially available cyclic olefin resin substrates may also be used. Examples of commercially available cyclic olefin resin substrates include cyclic olefin resin substrates such as "Escena (registered trademark)" and "SCA40 (registered trademark)" manufactured by Sekisui Chemical Co., Ltd.; cyclic olefin resin substrates such as "ZEONORFILM (registered trademark)" manufactured by OPTES Co., Ltd.; and cyclic olefin resin substrates such as "ARTONFILM (registered trademark)" manufactured by JSR Co., Ltd.
[0326] When there are hydroxyl and / or carboxyl groups on the substrate surface, the adhesion between the substrate and the vertically oriented liquid crystal solidified film can be improved by the pre-reaction compound contained in the vertically oriented liquid crystal solidified film, and a laminate having the most suitable adhesion and substrate peeling force P is obtained. Therefore, it is preferred that hydroxyl and / or carboxyl groups exist on the substrate surface constituting the laminate of the present invention. In order to set hydroxyl and carboxyl groups on the substrate surface, for example, corona treatment or plasma treatment can be implemented on the substrate surface, and hydroxyl and carboxyl groups are formed by oxidation of the substrate surface. In addition, for example, for triacetylcellulose film, saponification treatment can be utilized to post-treat the film, thereby forming hydroxyl and carboxyl groups. In order to ensure good adhesion with the vertically oriented liquid crystal solidified film, it is preferred that hydroxyl and / or carboxyl groups are uniformly present on the substrate surface. The surface treatment methods such as corona treatment, plasma treatment, and saponification treatment methods for forming hydroxyl and carboxyl groups on the substrate surface are not particularly limited, and can be carried out using the known methods used for the surface treatment of the substrate in the past. In addition, commercially available substrates that have been subjected to the above-mentioned treatment in advance on the substrate surface can also be selected and used.
[0327] In the present invention, the substrate is usually finally peeled off from the laminate of the present invention. By making the substrate peeling force P of the laminate satisfy the above formula (1), a laminate is obtained in which the substrate and the vertically aligned liquid crystal cured film are laminated with the most appropriate adhesion, and the vertically aligned liquid crystal cured film and the substrate are not easily peeled off during the cutting process of the laminate, but when the substrate is peeled off from the laminate, it can be peeled off cleanly with a small force.
[0328] The thickness of the substrate is usually 5 to 300 μm, preferably 10 to 150 μm, from the viewpoints of thinning the laminate, ease of peeling of the substrate, and handleability of the substrate.
[0329] The laminate of the present invention may include layers other than the substrate and the vertically oriented liquid crystal cured film within a range that does not affect the effect of the present invention. As such other layers, for example, a horizontally oriented phase difference film (horizontally oriented liquid crystal cured film), a horizontally oriented film, a cured resin layer added for the purpose of improving or reinforcing the mechanical strength of the liquid crystal cured film, a hard coating layer, etc. can be cited.
[0330] In the case of forming a laminated body by forming a vertically aligned liquid crystal cured film on a substrate, the present invention is also directed to a composition for forming a vertically aligned liquid crystal cured film comprising at least one selected from the group consisting of the following components, from the perspective of being suitable for producing a laminated body in which the substrate peeling force P satisfying the above-mentioned formula (1) is easily obtained, peeling between the vertically aligned liquid crystal cured film and the substrate is not likely to occur during the cutting process of the laminated body, but the substrate can be cleanly peeled off from the laminated body with a small force: (a1) a polymerizable liquid crystal compound; (a2) an ionic compound formed of non-metallic atoms as a vertical alignment promoter; and (a3) a compound having a functional group capable of reacting with a hydroxyl group or a carboxyl group and a (meth)acryloyl group in the molecule, and a polymerizable non-liquid crystal compound having two or more (meth)acryloyl groups.
[0331] As the polymerizable liquid crystal compound contained in the composition for forming a vertically oriented liquid crystal solidification film, the ionic compound formed by non-metallic atoms, and the compound having a functional group capable of reacting with a hydroxyl group or a carboxyl group and a (meth) acryloyl group in the molecule, and the polymerizable non-liquid crystal compound having more than 2 (meth) acryloyl groups, the same components as the components that can be included in the vertically oriented liquid crystal solidification film constituting the laminate of the present invention and the components exemplified above can be used. As a polymerizable liquid crystal compound, any of the polymerizable liquid crystal compounds of reverse wavelength dispersion and the polymerizable liquid crystal compounds of positive wavelength dispersion can be used. From the viewpoint of being able to further improve the adhesion, it is preferred to have a polymerizable liquid crystal compound of (meth) acryloyl groups. In addition, the composition for forming a vertically oriented liquid crystal solidification film can also include additives such as vertically oriented promoters, solvents, polymerization initiators, leveling agents, antioxidants, and photosensitizers other than the ionic compounds formed by non-metallic atoms. As these components, the same components as the components that can be included in the vertically oriented liquid crystal solidification film constituting the laminate of the present invention and the components exemplified above can be used.
[0332] [Method for producing laminate]
[0333] The laminate of the present invention can be produced, for example, by a method comprising the following steps:
[0334] A step of applying a polymerizable liquid crystal composition for forming a vertically aligned liquid crystal cured film containing a polymerizable liquid crystal compound on a substrate to obtain a coating film;
[0335] A step of drying the coating to form a dried coating; and
[0336] A step of irradiating the dried coating film with active energy rays to form a cured film of a vertically aligned liquid crystal.
[0337] The formation of the coating film of the vertically aligned liquid crystal cured film-forming composition can be performed by, for example, applying the vertically aligned liquid crystal cured film-forming composition on a substrate.
[0338] Examples of a method for applying the vertically aligned liquid crystal cured film-forming composition on a substrate include known methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and coater coating, and printing methods such as flexographic methods.
[0339] Then, the solvent is removed by drying, etc. to form a dry coating. As a drying method, natural drying, ventilation drying, heating drying and reduced pressure drying methods, etc. can be cited. At this time, by heating the coating obtained by the composition for forming a vertically aligned liquid crystal solidified film, the polymerizable liquid crystal compound can be oriented in a vertical direction relative to the plane of the coating while the solvent is dried and removed from the coating. In addition, by including a pre-reaction compound and a multifunctional (meth) acrylate compound, the hydroxyl group, carboxyl group and the functional group capable of reacting with a hydroxyl group or a carboxyl group present on the surface of the substrate react with the pre-reaction compound, and the (meth) acryloyl group possessed by the pre-reaction compound reacts with the polymerizable liquid crystal compound and the (meth) acryloyl group possessed by the multifunctional (meth) acrylate compound forming the vertically aligned liquid crystal solidified film, thereby forming a network structure between the substrate and the dry coating. The heating temperature of the coating can be appropriately determined by considering the polymerizable liquid crystal compound used and the material of the substrate to be formed, etc., but in order to make the polymerizable liquid crystal compound phase change into a liquid crystal phase state, it is usually necessary to be a temperature above the liquid crystal phase transition temperature. In order to remove the solvent contained in the composition for forming a vertically aligned liquid crystal curing film and simultaneously bring the polymerizable liquid crystal compound into a vertically aligned state, for example, the composition can be heated to a temperature near or above the liquid crystal phase transition temperature (smectic phase transition temperature or nematic phase transition temperature) of the polymerizable liquid crystal compound contained in the composition for forming a vertically aligned liquid crystal curing film.
[0340] It should be noted that the liquid crystal phase transition temperature can be measured using, for example, a polarizing microscope, a differential scanning calorimeter (DSC), a thermogravimetric differential thermal analyzer (TG-DTA), etc., equipped with a temperature regulating stage. In addition, when two or more polymerizable liquid crystal compounds are used in combination, the above-mentioned phase transition temperature refers to: a mixture of polymerizable liquid crystal compounds obtained by mixing all polymerizable liquid crystal compounds constituting the vertically aligned liquid crystal curing film-forming composition in the same ratio as the composition in the vertically aligned liquid crystal curing film-forming composition, and the temperature measured by operating in the same manner as when using one polymerizable liquid crystal compound. It should be noted that it is known that the following situation usually exists: the liquid crystal phase transition temperature of the polymerizable liquid crystal compound in the aforementioned vertically aligned liquid crystal curing film-forming composition is lower than the liquid crystal phase transition temperature of the polymerizable liquid crystal compound monomer.
[0341] The heating time can be appropriately determined depending on the heating temperature, the type of polymerizable liquid crystal compound used, the type of solvent, its boiling point and its amount, etc., and is usually 15 seconds to 10 minutes, preferably 0.5 to 5 minutes.
[0342] The removal of the solvent from the coating can be carried out simultaneously with the heating of the polymerizable liquid crystal compound to the liquid crystal phase transition temperature or above, or it can be carried out independently, but from the viewpoint of improving productivity, it is preferably carried out simultaneously. Before the heating of the polymerizable liquid crystal compound to the liquid crystal phase transition temperature or above is carried out, a pre-drying process can be provided for removing the solvent in the coating film appropriately under the condition that the polymerizable liquid crystal compound contained in the coating film obtained by the vertical alignment liquid crystal curing film forming composition is not polymerized. As the drying method in the pre-drying process, natural drying method, ventilation drying method, heating drying and reduced pressure drying method, etc. can be cited, and the drying temperature (heating temperature) in the drying process can be appropriately determined according to the type of polymerizable liquid crystal compound used, the type of solvent, its boiling point and its amount, etc.
[0343] Next, in the obtained dry coating, the polymerizable liquid crystal compound is polymerized while maintaining the vertical orientation state of the polymerizable liquid crystal compound, thereby forming a vertically oriented liquid crystal cured film. As a polymerization method, thermal polymerization and photopolymerization can be cited, but from the viewpoint of easy control of the polymerization reaction, photopolymerization is preferred. In photopolymerization, as the light irradiated to the dry coating, it can be appropriately selected according to the type of polymerization initiator contained in the dry coating, the type of polymerizable liquid crystal compound (especially the type of polymerizable group possessed by the polymerizable liquid crystal compound) and its amount. As a specific example, more than one light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α rays, β rays and γ rays, and active electron rays can be cited. Among them, from the aspect of easy control of the progress of the polymerization reaction, the device that can be used as a photopolymerization device and widely used in the art is considered, preferably ultraviolet light, preferably in a way that can be photopolymerized using ultraviolet light. The type of polymerizable liquid crystal compound and polymerization initiator contained in the composition for forming a vertically oriented liquid crystal cured film is pre-selected. In addition, during polymerization, by irradiating light while cooling the dried coating using appropriate cooling means, the polymerization temperature can also be controlled. If the polymerization of the polymerizable liquid crystal compound is implemented at a lower temperature by adopting such cooling means, even if a substrate with lower heat resistance is used, a vertically oriented liquid crystal cured film can be appropriately formed. In addition, within the range of the unfavorable conditions caused by the heat during light irradiation (deformation of the substrate due to heat, etc.), the polymerization reaction can also be promoted by increasing the polymerization temperature. During photopolymerization, by shielding, developing, etc., a patterned cured film can also be obtained.
[0344] As the light source of the aforementioned active energy line, for example, there can be mentioned a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source emitting light in the wavelength range of 380 to 440 nm, a chemical lamp, a black light lamp, a microwave-excited mercury lamp, a metal halide lamp, and the like.
[0345] UV radiation intensity is usually 10 to 3,000 mW / cm 2 The ultraviolet irradiation intensity is preferably an intensity in the wavelength region effective for activating the photopolymerization initiator. The irradiation time is usually 0.1 second to 10 minutes, preferably 0.1 second to 5 minutes, more preferably 0.1 second to 3 minutes, and further preferably 0.1 second to 1 minute. When irradiation is performed once or more times with such an ultraviolet irradiation intensity, the cumulative light amount is 10 to 3,000 mJ / cm 2 , preferably 50 to 2,000 mJ / cm 2 , more preferably 100 to 1,000 mJ / cm 2 .
[0346] The thickness of the vertically aligned liquid crystal cured film can be appropriately selected depending on the display device to which it is applied, and is preferably 0.3 μm or more and 5.0 μm or less, more preferably 3.0 μm or less, and further preferably 2.0 μm or less.
[0347] 〔Horizontal orientation phase difference film〕
[0348] The laminate of the present invention may include a horizontally oriented phase difference film. The horizontally oriented phase difference film that can constitute the laminate of the present invention refers to a phase difference film oriented in the horizontal direction relative to the in-plane direction of the vertically oriented liquid crystal cured film, for example, it can be a stretched film, a cured product of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound, that is, a cured product formed by curing the polymerizable liquid crystal compound in a state of being oriented in the horizontal direction relative to the plane of the phase difference film (hereinafter, also referred to as a "horizontally oriented liquid crystal cured film"), etc.
[0349] In the present invention, the horizontally aligned retardation film preferably satisfies the following formula (6).
[0350] ReA(450) / ReA(550)≤1.0 (6)
[0351] [In formula (6), ReA(λ) represents the in-plane phase difference value of the horizontally oriented phase difference film at a wavelength of λnm, ReA(λ) = (nxA(λ) - nyA(λ)) × dA (where nxA(λ) represents the principal refractive index at a wavelength of λnm in the plane of the horizontally oriented phase difference film, nyA(λ) represents the refractive index at a wavelength of λnm in a direction orthogonal to the direction of nxA in the same plane as nxA, and dA represents the film thickness of the horizontally oriented phase difference film)]
[0352] When the horizontally oriented phase difference film satisfies formula (6), the horizontally oriented phase difference film shows a so-called reverse wavelength dispersion in which the in-plane phase difference value at a short wavelength is smaller than the in-plane phase difference value at a long wavelength. By combining such a horizontally oriented phase difference film with the above-mentioned vertically oriented liquid crystal curing film, a laminate having excellent improvement effect of the front and oblique reflection hue when the black display is assembled to an organic EL display device can be obtained. Since the reverse wavelength dispersion can be improved and the improvement effect of the reflection hue in the front direction of the horizontally oriented phase difference film can be further improved, ReA (450) / ReA (550) is preferably 0.70 or more, more preferably 0.78 or more, and preferably 0.95 or less, more preferably 0.92 or less.
[0353] The above-mentioned in-plane phase difference value can be adjusted by the thickness dA of the horizontally oriented phase difference film. The in-plane phase difference value is determined by the above formula ReA(λ) = (nxA(λ)-nyA(λ))×dA. Therefore, in order to obtain the desired in-plane phase difference value (ReA(λ): the in-plane phase difference value of the horizontally oriented phase difference film at wavelength λ (nm)), it is sufficient to adjust the three-dimensional refractive index and the film thickness dA.
[0354] In addition, the horizontally aligned retardation film preferably satisfies the following formula (7).
[0355] 120nm≤ReA(550)≤170nm (7)
[0356] [In formula (7), ReA(λ) has the same meaning as above]
[0357] When the in-plane phase difference ReA(550) of the horizontally oriented phase difference film is within the range of formula (7), the effect of improving the front reflection hue (effect of suppressing coloration) during black display when the laminate (elliptically polarizing plate) including the horizontally oriented phase difference film is applied to an organic EL display device becomes significant. A further preferred range of the in-plane phase difference value is 130nm≤ReA(550)≤150nm.
[0358] From the perspective of being able to easily control the desired phase difference of the phase difference film and being able to achieve thin filmization, it is preferred that the horizontally oriented phase difference film is a horizontally oriented liquid crystal cured film. As a polymerizable liquid crystal compound for forming a horizontally oriented liquid crystal cured film, a polymerizable liquid crystal compound previously known in the field of the phase difference film can be used. Specifically, a compound represented by formula (X) and / or (Y) as an example of a polymerizable liquid crystal compound that can be used in the formation of a vertically oriented liquid crystal cured film can be used, wherein a polymerizable liquid crystal compound preferably showing so-called reverse wavelength dispersion, for example, a compound represented by the above formula (X) can be appropriately used. In the polymerizable liquid crystal composition for forming a horizontally oriented liquid crystal cured film, the polymerizable liquid crystal compound can be used alone or in combination of two or more.
[0359] The content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition used in the formation of the horizontally aligned liquid crystal cured film is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and further preferably 90 to 95 parts by mass, relative to 100 parts by mass of the solid content of the polymerizable liquid crystal composition. When the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the viewpoint of the orientation of the obtained liquid crystal cured film.
[0360] The polymerizable liquid crystal composition used in the formation of the horizontal alignment liquid crystal cured film may contain additives such as a solvent, a photopolymerization initiator, a leveling agent, an antioxidant, and a photosensitizer in addition to the polymerizable liquid crystal compound. As these components, the same components as those exemplified above as components that can be used in the vertical alignment liquid crystal cured film can be cited, and only one of each can be used, or two or more can be used in combination.
[0361] The polymerizable liquid crystal composition for forming a horizontally aligned liquid crystal cured film can be obtained by stirring a polymerizable liquid crystal compound and components other than the polymerizable liquid crystal compound, such as a solvent and a photopolymerization initiator, at a predetermined temperature.
[0362] The horizontally aligned liquid crystal cured film can be produced, for example, by a method including the following steps:
[0363] A step of applying a polymerizable liquid crystal composition for forming a horizontal alignment liquid crystal cured film onto a substrate or a horizontal alignment film to obtain a coating film;
[0364] a step of drying the coating to form a dried coating; and
[0365] A step of irradiating the dried coating film with active energy rays to form a horizontally aligned liquid crystal cured film.
[0366] The formation of the coating film of the polymerizable liquid crystal composition can be carried out, for example, by coating the polymerizable liquid crystal composition for forming a horizontally aligned liquid crystal cured film on a substrate, a horizontally aligned film described later, etc. As the substrate that can be used therein, the same substrate as the substrate exemplified above as the substrate that can be used in the formation of a vertically aligned liquid crystal cured film can be used.
[0367] Next, the solvent is removed by drying, etc., thereby forming a dry coating. As drying methods, natural drying, ventilation drying, heating drying and reduced pressure drying methods can be cited. From the perspective of productivity, heating drying is preferred, and the heating temperature at this time is preferably able to remove the solvent and is above the phase transition temperature of the polymerizable liquid crystal compound. The steps and conditions in this process can be cited as the same steps and conditions that can be adopted in the method for manufacturing a vertically oriented liquid crystal cured film.
[0368] The obtained dried coating film is irradiated with active energy rays (more specifically, ultraviolet rays, etc.), and the polymerizable liquid crystal compound is polymerized while maintaining the state of being oriented in the horizontal direction relative to the coating film plane, thereby forming a horizontally oriented liquid crystal cured film. As a polymerization method, the same method as that used in the method for producing a vertically oriented liquid crystal cured film can be cited.
[0369] The thickness of the horizontally aligned liquid crystal cured film can be appropriately selected depending on the display device to which it is applied, and is preferably 0.2 to 5 μm, more preferably 0.2 to 4 μm, and further preferably 0.2 to 3 μm.
[0370] By forming a coating of a polymerizable liquid crystal compound on a horizontal alignment film, the orientation of the polymerizable liquid crystal compound in the horizontal direction can be further improved. For example, in the case where a horizontal alignment film is formed on a vertical alignment liquid crystal curing film constituting the laminate of the present invention and a polymerizable liquid crystal composition for forming a horizontal alignment liquid crystal curing film is applied thereon to obtain a horizontal alignment liquid crystal curing film, compared with a method in which a horizontal alignment liquid crystal curing film is formed on a substrate or a horizontal alignment film (which is arranged on the substrate) and then bonded to a vertical alignment liquid crystal curing film via an adhesive layer, it also has the advantage of being able to simplify the manufacturing process of the laminate. The horizontal alignment film can be appropriately selected from a material having a horizontal alignment control force that allows the polymerizable liquid crystal compound to be oriented in the horizontal direction relative to the coating plane. The alignment control force can be arbitrarily adjusted by the type of alignment film, the surface state, the friction conditions, etc., and in the case of being formed by a photo-aligned polymer, it can be arbitrarily adjusted by polarized light irradiation conditions, etc.
[0371] As a horizontal alignment film, it is preferred to have solvent resistance that does not dissolve due to the coating of the polymerizable liquid crystal composition, etc., and heat resistance in the heating treatment for removing the solvent and aligning the polymerizable liquid crystal compound described later. As alignment films, alignment films including alignment polymers, photoalignment films, groove alignment films having a concave-convex pattern and multiple grooves on the surface, and stretched films stretched along the alignment direction can be cited. From the perspective of the accuracy and quality of the orientation angle, photoalignment films are preferred.
[0372] As the oriented polymer, for example, polyamides, gelatins, polyimides having amide bonds in the molecule and polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinyl pyrrolidone, polyacrylic acid and polyacrylates as their hydrolyzates can be cited. Among them, polyvinyl alcohol is preferred. The oriented polymer can be used alone or in combination of two or more.
[0373] An oriented film containing an oriented polymer can be generally obtained by applying a composition in which an oriented polymer is dissolved in a solvent (hereinafter, sometimes referred to as an "oriented polymer composition") to a substrate and removing the solvent; or by applying the oriented polymer composition to a substrate, removing the solvent, and rubbing (rubbing method). As the solvent, the same solvent as the solvent exemplified above as a solvent that can be used in a polymerizable liquid crystal composition for forming a horizontally oriented liquid crystal cured film can be cited.
[0374] The concentration of the oriented polymer in the oriented polymer composition may be within a range in which the oriented polymer material can be completely dissolved in the solvent, and is preferably about 0.1 to 20%, more preferably about 0.1 to 10%, in terms of solid content relative to the solution.
[0375] As the oriented polymer composition, a commercially available oriented film material may be used as it is. Examples of commercially available oriented film materials include SUNEVER (registered trademark, manufactured by Nissan Chemical Industries, Ltd.) and OPTOMER (registered trademark, manufactured by JSR Corporation).
[0376] As a method for applying the oriented polymer composition to a substrate, the same method as the method exemplified as the method for applying the polymerizable liquid crystal composition for forming a horizontally aligned liquid crystal cured film to a substrate can be mentioned.
[0377] Examples of a method for removing the solvent contained in the oriented polymer composition include a natural drying method, a ventilation drying method, a heat drying method, and a reduced pressure drying method.
[0378] In order to impart an orientation restricting force to the oriented film, a rubbing treatment (rubbing method) may be performed as required. As a method of imparting an orientation restricting force by rubbing, there can be cited a method of bringing an oriented polymer film formed on the surface of a substrate by coating an oriented polymer composition on a substrate and annealing the oriented polymer composition into contact with a rubbing roller wound with a rubbing cloth and rotating. When performing the rubbing treatment, if masking is performed, multiple regions (patterns) with different orientation directions can also be formed in the oriented film.
[0379] The photo-alignment film can be generally obtained by applying a composition containing a polymer or monomer having a photoreactive group and a solvent (hereinafter also referred to as a "photo-alignment film-forming composition") to a substrate, removing the solvent, and then irradiating the substrate with polarized light (preferably polarized UV light). The photo-alignment film is advantageous in that the direction of the orientation restraining force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.
[0380] The so-called photoreactive group refers to a group that generates liquid crystal orientation ability by light irradiation. Specifically, groups that participate in the photoreaction of the orientation induction or isomerization reaction, dimerization reaction, photocrosslinking reaction or photodecomposition reaction of molecules that occur by light irradiation, which become the source of liquid crystal orientation ability, can be cited. Among them, the group participating in the dimerization reaction or the photocrosslinking reaction is preferred from the aspect of excellent orientation. As a photoreactive group, it is preferably a group having an unsaturated bond, especially a double bond, and it is particularly preferred to have at least one group selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond) and a carbon-oxygen double bond (C=O bond).
[0381] As photoreactive groups having C=C bonds, vinyl, polyene, stilbene, stilbazole, stilbazolium, chalcone, and cinnamoyl groups can be cited. As photoreactive groups having C=N bonds, groups having structures such as aromatic Schiff bases and aromatic hydrazones can be cited. As photoreactive groups having N=N bonds, azophenyl, azonaphthyl, aromatic heterocyclic azo, bisazo, formazan, and groups having an oxidized azobenzene structure can be cited. As photoreactive groups having C=O bonds, benzophenone, coumarin, anthraquinone, and maleimide groups can be cited. These groups can have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid, and halogenated alkyl.
[0382] Among them, photoreactive groups that participate in the photodimerization reaction are preferred, and cinnamoyl and chalcone groups are preferred from the perspective of the small amount of polarized light irradiation required for photo-alignment and the ease of obtaining a photo-alignment film with excellent thermal stability and temporal stability. As a polymer having a photoreactive group, a polymer having a cinnamoyl group at the end of the polymer side chain that forms a cinnamic acid structure is particularly preferred.
[0383] By applying the photo-alignment film-forming composition on a substrate, a photo-alignment inducing layer can be formed on the substrate. The solvent contained in the composition may be the same solvent as the solvent used in the polymerizable liquid crystal composition for forming a horizontally aligned liquid crystal cured film and may be appropriately selected according to the solubility of the polymer or monomer having a photoreactive group.
[0384] The content of the polymer or monomer having a photoreactive group in the composition for forming a photo-alignment film can be appropriately adjusted according to the type of the polymer or monomer and the thickness of the target photo-alignment film, and is preferably at least 0.2% by mass, more preferably in the range of 0.3 to 10% by mass, relative to the mass of the composition for forming a photo-alignment film. The composition for forming a photo-alignment film can contain a polymer material such as polyvinyl alcohol and polyimide, and a photosensitizer within a range that does not significantly impair the properties of the photo-alignment film.
[0385] As a method for applying the photo-alignment film-forming composition to a substrate, the same method as the method for applying the oriented polymer composition to a substrate can be cited. As a method for removing the solvent from the applied photo-alignment film-forming composition, for example, natural drying, ventilation drying, heating drying, and reduced pressure drying can be cited.
[0386] In order to irradiate polarized light, it can be a form of directly irradiating polarized UV light to the product obtained by removing the solvent from the composition for forming a photo-alignment film applied on the substrate, or it can be a form of irradiating polarized light from the substrate side and allowing the polarized light to pass through to irradiate. In addition, the polarized light is particularly preferably substantially parallel light. The wavelength of the irradiated polarized light is the wavelength of the wavelength region in which the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) in the range of 250 to 400nm is particularly preferred. As a light source for the polarized light irradiation, xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, ultraviolet lasers such as KrF and ArF can be cited, and high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are more preferred. Among these, high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are preferred because of the large luminous intensity of ultraviolet rays with a wavelength of 313nm. Polarized UV light can be irradiated by irradiating the light from the aforementioned light source through an appropriate polarizer. As the polarizer, a polarizing filter, a polarizing prism such as Glan-Thompson or Glan-Taylor, or a wire grid type polarizer can be used.
[0387] In addition, when rubbing or polarized light irradiation is performed, if shielding is performed, a plurality of regions (patterns) in which the directions of liquid crystal alignment are different can be formed.
[0388] The groove oriented film is a film having a concave-convex pattern or multiple grooves (grooves) on the film surface. When a polymerizable liquid crystal compound is applied to a film having multiple linear grooves arranged at equal intervals, the liquid crystal molecules are oriented in the direction along the grooves.
[0389] As methods for obtaining a groove-oriented film, the following methods can be cited: a method of exposing the surface of a photosensitive polyimide film through an exposure mask having a slit in a pattern shape, and then performing development and rinsing treatment to form a concave-convex pattern; a method of forming a layer of a UV-curable resin before curing on a plate-shaped original plate having grooves on the surface, transferring the formed resin layer to a substrate, and then curing it; and a method of pushing a roller-shaped original plate having multiple grooves against a film of a UV-curable resin before curing formed on a substrate to form concave-convex, and then curing it; and the like.
[0390] In the laminate of the present invention, the vertically aligned liquid crystal curing film and the horizontally aligned phase difference film can be stacked via, for example, an adhesive layer and an adhesive layer. As an adhesive or an adhesive, a material previously known in the field can be used. In addition, a polymerizable liquid crystal composition for forming a horizontally aligned liquid crystal curing film can be applied to the vertically aligned liquid crystal curing film constituting the laminate of the present invention with or without a horizontally aligned film, thereby stacking a horizontally aligned phase difference film (horizontally aligned liquid crystal curing film) on the vertically aligned liquid crystal curing film.
[0391] 〔Elliptical polarizing plate〕
[0392] The present invention includes an elliptically polarizing plate comprising the laminate of the present invention and a polarizing film.
[0393] The polarizing film includes a film having a polarizing function, a stretched film adsorbed with a dye having absorption anisotropy, a film including a film coated with a dye having absorption anisotropy as a polarizer, etc. As the dye having absorption anisotropy, for example, a dichroic dye can be mentioned.
[0394] For a film that includes a stretched film adsorbed with a dye having absorption anisotropy as a polarizer, it is usually produced by clamping a transparent protective film on at least one side of the following polarizer via an adhesive, and the polarizer is manufactured through the following steps: a step of uniaxially stretching a polyvinyl alcohol resin film; a step of dyeing the polyvinyl alcohol resin film with a dichroic dye so that it adsorbs the dichroic dye; a step of treating the polyvinyl alcohol resin film adsorbed with the dichroic dye with an aqueous boric acid solution; and a step of washing with water after the treatment with the aqueous boric acid solution.
[0395] The polyvinyl alcohol resin is obtained by saponifying a polyvinyl acetate resin. As the polyvinyl acetate resin, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith can be used. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having an ammonium group.
[0396] The saponification degree of the polyvinyl alcohol resin is generally about 85 to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, for example, polyvinyl formal and polyvinyl acetal modified with aldehydes may be used. The degree of polymerization of the polyvinyl alcohol resin is generally about 1,000 to 10,000, preferably in the range of 1,500 to 5,000.
[0397] The film made of such a polyvinyl alcohol resin can be used as a raw film of a polarizing film. The method of making a polyvinyl alcohol resin into a film is not particularly limited, and the film can be made by a known method. The film thickness of the polyvinyl alcohol raw film can be, for example, about 10 to 150 μm.
[0398] The uniaxial stretching of the polyvinyl alcohol resin film can be performed before, at the same time as, or after dyeing based on a dichroic pigment. In the case of uniaxial stretching after dyeing, the uniaxial stretching can be performed before or during the boric acid treatment. In addition, the uniaxial stretching can be performed in multiple stages thereof. When the uniaxial stretching is performed, the uniaxial stretching can be performed between rollers having different peripheral speeds, or the uniaxial stretching can be performed using a hot roller. In addition, the uniaxial stretching can be dry stretching performed in the atmosphere, or wet stretching performed in a state where the polyvinyl alcohol resin film is swollen with a solvent. The stretching ratio is usually about 3 to 8 times.
[0399] The polyvinyl alcohol-based resin film can be dyed with a dichroic dye by, for example, a method of immersing the polyvinyl alcohol-based resin film in an aqueous solution containing a dichroic dye.
[0400] As the dichroic pigment, specifically, iodine and dichroic organic dyes can be used. As the dichroic organic dyes, dichroic direct dyes formed by disazo compounds such as CI Direct Red (DIRECT RED) 39, and dichroic direct dyes formed by compounds such as triazo and tetrakis azo can be cited. For the polyvinyl alcohol-based resin film, it is preferably immersed in water before dyeing.
[0401] When iodine is used as a dichroic pigment, a method of dyeing a polyvinyl alcohol-based resin film by immersing it in an aqueous solution containing iodine and potassium iodide can generally be adopted. The content of iodine in the aqueous solution is generally about 0.01 to 1 part by mass relative to 100 parts by mass of water. In addition, the content of potassium iodide is generally about 0.5 to 20 parts by mass relative to 100 parts by mass of water. The temperature of the aqueous solution used for dyeing is generally about 20 to 40°C. In addition, the immersion time (dyeing time) in the aqueous solution is generally about 20 to 1,800 seconds.
[0402] On the other hand, when a dichroic organic dye is used as the dichroic pigment, a method of dyeing the polyvinyl alcohol-based resin film by immersing the film in an aqueous solution containing a water-soluble dichroic dye can be generally adopted. The content of the dichroic organic dye in the aqueous solution is generally 1×10 -4 ~10 parts by mass, preferably 1×10 -3 ~1 mass part, more preferably 1×10 -3 ~1×10 -2 The aqueous solution may contain an inorganic salt such as sodium sulfate as a dyeing auxiliary. The temperature of the dichroic dye aqueous solution used for dyeing is usually about 20 to 80° C. In addition, the immersion time (dyeing time) in the aqueous solution is usually about 10 to 1,800 seconds.
[0403] Boric acid treatment after dyeing based on dichroic pigments can usually be carried out by immersing the dyed polyvinyl alcohol-based resin film in an aqueous solution of boric acid. The content of boric acid in the aqueous solution of boric acid is usually about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, relative to 100 parts by mass of water. When iodine is used as a dichroic pigment, the aqueous solution of boric acid preferably contains potassium iodide, and the content of potassium iodide at this time is usually about 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, relative to 100 parts by mass of water. The immersion time in the aqueous solution of boric acid is usually about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid treatment is usually above 50°C, preferably 50 to 85°C, and more preferably 60 to 80°C.
[0404] Generally, the polyvinyl alcohol-based resin film treated with boric acid can be subjected to a water washing treatment. The water washing treatment can be performed, for example, by immersing the polyvinyl alcohol-based resin film treated with boric acid in water. The temperature of water in the water washing treatment is generally about 5 to 40° C. In addition, the immersion time is generally about 1 to 120 seconds.
[0405] A drying treatment can be performed after washing to obtain a polarizer. The drying treatment can be performed, for example, using a hot air dryer or a far-infrared heater. The temperature of the drying treatment is usually about 30 to 100°C, preferably 50 to 80°C. The time of the drying treatment is usually about 60 to 600 seconds, preferably 120 to 600 seconds. By drying, the moisture content of the polarizer can be reduced to a practical level. Its moisture content is usually about 5 to 20% by weight, preferably 8 to 15% by weight. When the moisture content is lower than 5% by weight, the flexibility of the polarizer is lost, and after the polarizer is dried, it is sometimes damaged or broken. In addition, when the moisture content is higher than 20% by weight, there is a possibility that the thermal stability of the polarizer will deteriorate.
[0406] The thickness of the polarizer obtained by uniaxially stretching the polyvinyl alcohol-based resin film, dyeing it with a dichroic dye, treating it with boric acid, washing it with water, and drying it as described above is preferably 5 to 40 μm.
[0407] As the film coated with the pigment having absorption anisotropy, there can be cited a film obtained by coating a composition containing a dichroic pigment having liquid crystal properties, or a composition containing a dichroic pigment and a polymerizable liquid crystal, etc. The film preferably has a protective film on one or both sides thereof. As the protective film, there can be cited a film identical to the resin film exemplified in the above text as a base material that can be used in the manufacture of a vertically aligned liquid crystal cured film.
[0408] The film coated with the dye having absorption anisotropy is preferably as thin as possible, but if it is too thin, the strength tends to decrease and the processability tends to be poor. The thickness of the film is usually 20 μm or less, preferably 5 μm or less, and more preferably 0.5 to 3 μm.
[0409] Specific examples of the film formed by coating a dye having absorption anisotropy include films described in JP-A-2012-33249 and the like.
[0410] A transparent protective film may be laminated on at least one side of the polarizer obtained as described above via, for example, an adhesive layer. As the transparent protective film, the same transparent film as the resin film exemplified above as a substrate usable in the manufacture of a vertically aligned liquid crystal cured film may be used.
[0411] The elliptically polarizing plate of the present invention is composed of a laminate of the present invention, or a laminate after removing a substrate from the laminate of the present invention and a polarizing film. For example, the elliptically polarizing plate of the present invention can be obtained by laminating the laminate of the present invention and the polarizing film via an adhesive layer, etc. In addition, the elliptically polarizing plate of the present invention can be obtained by laminating the laminate after removing a substrate from the laminate of the present invention and the polarizing film.
[0412] In one embodiment of the present invention, when the laminate of the present invention including the horizontally aligned retardation film is laminated with a polarizing film, it is preferred that the laminate be laminated so that the angle formed by the slow axis (optical axis) of the horizontally aligned retardation film constituting the laminate and the absorption axis of the polarizing film is 45±5°.
[0413] The elliptically polarizing plate of the present invention may have a conventional elliptically polarizing plate, or a structure such as a polarizing film and a phase difference film. As such a structure, for example, an adhesive layer (sheet) for attaching the elliptically polarizing plate to a display element such as an organic EL, a protective film used for protecting the surface of the polarizing film and the liquid crystal cured film from damage and contamination, etc. may be cited.
[0414] The laminate and elliptically polarizing plate of the present invention can be used in various display devices.
[0415] The so-called display device is a device having a display element, including a light-emitting element or a light-emitting device as a light source. Examples of display devices include liquid crystal display devices, organic electroluminescent (EL) display devices, inorganic electroluminescent (EL) display devices, touch panel display devices, electron emission display devices (such as field emission display devices (FED), surface field emission display devices (SED)), electronic paper (display devices using electronic ink and electrophoretic elements, plasma display devices, projection display devices (such as grating light valve (GLV) display devices, display devices with digital micromirror devices (DMD)) and piezoelectric ceramic displays. Liquid crystal display devices also include transmissive liquid crystal display devices, semi-transmissive liquid crystal display devices, reflective liquid crystal display devices, and the like. Any of a liquid crystal display device, a direct-view liquid crystal display device, and a projection-type liquid crystal display device. These display devices can be display devices that display two-dimensional images, or they can be stereoscopic display devices that display three-dimensional images. In particular, with respect to the elliptically polarizing plate of the present invention, due to the small orientation defects and excellent optical properties, it can be suitably used in an organic electroluminescent (EL) display device, and the laminate of the present invention can be suitably used in a liquid crystal display device and a touch panel display device. By using the laminate or elliptically polarizing plate of the present invention, it is easy to realize the thinning of the display device, and a display device with excellent optical properties and good image display characteristics can be obtained.
[0416] Example
[0417] Hereinafter, the present invention will be described in more detail by way of Examples. It should be noted that, unless otherwise specified, "%" and "parts" in the examples refer to mass % and mass parts, respectively.
[0418] 1. Embodiment 1
[0419] (1) Preparation of polymerizable liquid crystal compounds
[0420] A polymerizable liquid crystal compound (X1) and a polymerizable liquid crystal compound (X2) having the following molecular structures were prepared respectively. The polymerizable liquid crystal compound (X1) was prepared according to the method described in Japanese Patent Publication No. 2010-31223. In addition, the polymerizable liquid crystal compound (X2) was prepared according to the method described in Japanese Patent Publication No. 2009-173893.
[0421] Polymerizable liquid crystal compound (X1)
[0422]
[0423] 1 mg of the polymerizable liquid crystal compound (X1) was dissolved in 50 mL of tetrahydrofuran to obtain a solution. The obtained solution was placed in a measuring cuvette with an optical path of 1 cm as a measuring sample, and the measuring sample was placed in an ultraviolet-visible spectrophotometer ("UV-2450" manufactured by Shimadzu Corporation) to measure the absorption spectrum. The wavelength of the maximum absorbance was read from the obtained absorption spectrum. As a result, the maximum absorption wavelength λ in the wavelength range of 300 to 400 nm was max It is 350nm.
[0424] Polymerizable liquid crystal compound (X2)
[0425]
[0426] (2) Preparation of a composition for forming a vertically aligned liquid crystal cured film
[0427] A mixed solution of 13 parts by mass of "KBE-903" manufactured by Shin-Etsu Chemical Co., Ltd. and 87 parts by mass of cyclopentanone and a mixed solution of 13 parts by mass of "Karenz MOI-EG" manufactured by Showa Denko K.K. and 87 parts by mass of cyclopentanone were mixed so as to obtain KBE-903:Karenz MOI-EG=1.00:1.35 (mass ratio), and then kept warm at 30°C for 16 hours to obtain a mixed solution (hereinafter sometimes referred to as mixed solution (1)) containing the following compound (preliminary reaction compound), wherein the compound has a functional group (hydroxysilyl group) capable of reacting with a hydroxyl group or a carboxyl group and a (meth)acryloyl group (acryloyl group) in the molecule.
[0428] Next, the polymerizable liquid crystal compound (X1) and the polymerizable liquid crystal compound (X2) were mixed at a mass ratio of 90:10 to obtain a mixture. With respect to 100 parts by mass of the obtained mixture, 0.25 parts by mass of a leveling agent "F-556" (manufactured by DIC Corporation), 2.0 parts by mass of an ionic compound A (molecular weight: 645) prepared with reference to Japanese Patent Application No. 2016-514802, 6 parts by mass of Irgacure 369E (manufactured by BASF Japan Co., Ltd.) as a photopolymerization initiator, and 0.5 parts by mass of "APG-700" (bifunctional, molecular weight: 808) manufactured by Shin-Nakamura Chemical Co., Ltd. as a polymerizable non-liquid crystal compound having two or more (meth)acryloyl groups were added, and N-methyl-2-pyrrolidone (NMP) was added so that the solid content concentration became 13%. Furthermore, a compound (pre-reaction compound) having a functional group capable of reacting with a hydroxyl group or a carboxyl group and a (meth)acryloyl group in the molecule is added in an amount of 2.35 parts by mass relative to 100 parts by mass of the mixture of the polymerizable liquid crystal compounds (X1) and (X2) to obtain a mixture. The obtained mixture is stirred at 80° C. for 1 hour to obtain a composition for forming a vertically aligned liquid crystal cured film.
[0429] Ionic compound A:
[0430]
[0431] (3) Production of vertically aligned liquid crystal cured film
[0432] A COP film (ZF14-50) manufactured by Zeon Co., Ltd. was subjected to a corona treatment, and then the above-mentioned composition for forming a vertically aligned liquid crystal cured film was applied using a bar coater. After heating at 120° C. for 90 seconds, a high-pressure mercury lamp (Unicure VB-15201BY-A, manufactured by Ushio Electric Co., Ltd.) was used to irradiate the surface on which the composition for forming a vertically aligned liquid crystal cured film was applied with ultraviolet rays (in a nitrogen atmosphere, the cumulative light amount at a wavelength of 365 nm: 500 mJ / cm 2 ) to form a vertically aligned liquid crystal cured film. The film thickness of the obtained vertically aligned liquid crystal cured film was measured using an ellipsometer (M-220 manufactured by JASCO Corporation) and found to be 1.2 μm.
[0433] <Rth measurement of vertically aligned liquid crystal cured film>
[0434] The vertically oriented liquid crystal curing film surface of the laminate comprising a substrate and a vertically oriented liquid crystal curing film prepared by the above steps is subjected to corona treatment, and after being bonded to the glass via a 25μm pressure-sensitive adhesive manufactured by LINTEC, the substrate is peeled off. For the obtained laminate comprising glass, adhesive, and vertically oriented liquid crystal curing film, KOBRA-WPR manufactured by Prince Instruments Co., Ltd. is used to change the incident angle of light to the sample for optical property measurement, and the front phase difference value and the phase difference value when tilted 40° with the fast axis as the center are measured. The average refractive index at each wavelength is measured using an ellipsometer M-220 manufactured by JASCO Corporation. In addition, the film thickness is measured using the OpticalNanoGauge film thickness meter C12562-01 manufactured by Hamamatsu Photonics Co., Ltd. The three-dimensional refractive index was calculated from the above-mentioned front phase difference value, the phase difference value when tilted 40° around the fast axis, the average refractive index, and the film thickness, with reference to the Oji Instruments Technical Data (http: / / www.oji-keisoku.co.jp / products / kobra / reference.html). The optical properties of each vertically aligned liquid crystal cured film were calculated according to the following formula based on the obtained three-dimensional refractive index. The results are shown in Table 1.
[0435] RthC(λ)=((nxC(λ)+nyC(λ)) / 2-nzC(λ))×dC
[0436] It should be noted that RthC(λ) represents the phase difference value in the film thickness direction of the vertically aligned liquid crystal cured film at a wavelength of λnm. In addition, nxC(λ) represents the in-plane principal refractive index of the vertically aligned liquid crystal cured film at a wavelength of λnm, nyC(λ) represents the refractive index in the direction orthogonal to nxC(λ) in the plane at a wavelength of λnm, nzC(λ) represents the refractive index in the thickness direction of the vertically aligned liquid crystal cured film at a wavelength of λnm, and when nxC(λ)=nyC(λ), nxC(λ) can be set to the refractive index in any direction in the film plane, and dC represents the film thickness of the vertically aligned liquid crystal cured film.
[0437] <Measurement of Substrate Peel Force>
[0438] After the vertically oriented liquid crystal curing film side of the laminate comprising the above-mentioned vertically oriented liquid crystal curing film and the substrate is subjected to corona treatment, it is bonded to a glass of 12 cm long × 10 cm wide × 0.7 mm thick via a 15 μm pressure-sensitive adhesive manufactured by LINTEC (composition: substrate / vertical oriented liquid crystal curing film / adhesive layer / glass). For the obtained sample, a 2.5 cm wide incision is made from the substrate side using a cutter. The prepared sample is placed on an Autograph "EZ-L" manufactured by Shimadzu Corporation, and a 2.5 cm wide substrate is peeled off at a speed of 300 mm / minute in a direction parallel to the glass surface, and the peeling force at this time is confirmed. The results are shown in Table 1.
[0439] <Evaluation of the end portion during cutting>
[0440] After corona treatment was applied to the vertically oriented liquid crystal curing film side of the laminate comprising the vertically oriented liquid crystal curing film and the substrate, it was bonded to a glass of 12 cm long × 10 cm wide × 0.7 mm thick via a 15 μm pressure-sensitive adhesive manufactured by LINTEC (composition: substrate / vertical oriented liquid crystal curing film / adhesive layer / glass). For the obtained sample, a 10 cm wide incision was made from the substrate side using a cutter, and the obtained cut surface was observed using a microscope ("BX-51" manufactured by Olympus Corporation). 11 points were observed every 1 cm, and the shortest distance from the cut surface to the position where the substrate bulged was measured. The average value of the data of the 11 points was used as the end bulge length, and the end was evaluated during the cutting process according to the following criteria. The results are shown in Table 1.
[0441] Evaluation Benchmarks
[0442] ○: less than 100 μm
[0443] △: 100μm or more and less than 200μm
[0444] ×: 200 μm or more
[0445] 2. Examples 2 to 4
[0446] When preparing the vertically aligned liquid crystal cured film-forming composition, samples were prepared and evaluated in the same manner as in Example 1 except that the addition amount of "APG-700" as the polyfunctional (meth)acrylate compound was changed as described in Table 1. The results are shown in Table 1.
[0447] 3. Example 5
[0448] When preparing the vertical alignment liquid crystal cured film-forming composition, a sample was prepared and evaluated in the same manner as in Example 1 except that 3.0 parts by mass of "A-DPH" (6-functional, molecular weight: 578) manufactured by Shin-Nakamura Chemical Co., Ltd. was added instead of APG-700. The results are shown in Table 1.
[0449] 4. Example 6
[0450] The results are shown in Table 1, except that APG-700 was not added (that is, polyfunctional (meth)acrylate was not blended) when preparing the vertically aligned liquid crystal cured film-forming composition, a sample was prepared and evaluated in the same manner as in Example 1.
[0451] 5. Comparative Example 1
[0452] The results are shown in Table 1, except that the vertically aligned liquid crystal cured film-forming composition was prepared as follows.
[0453] (1) Preparation of a composition for forming a vertically aligned liquid crystal cured film
[0454] The polymerizable liquid crystal compound (X1) and the polymerizable liquid crystal compound (X2) are mixed in a mass ratio of 90:10 to obtain a mixture. With respect to 100 parts by mass of the obtained mixture, 2.0 parts by mass of an ionic compound A (molecular weight: 645) prepared with reference to Japanese Patent Application No. 2016-514802, 0.5 parts by mass of a silane coupling agent "KBE-9103" (manufactured by Shin-Etsu Chemical Co., Ltd.), and 6 parts by mass of 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)-1-butanone (manufactured by BASF Japan Co., Ltd. "Irgacure (registered trademark) 369 (Irg369)") as a photopolymerization initiator are added. Furthermore, N-methyl-2-pyrrolidone (NMP) is added in such a way that the solid content concentration becomes 13%. The mixture is stirred at 80°C for 1 hour to obtain a composition for forming a vertically aligned liquid crystal curing film.
[0455] [Table 1]
[0456]
[0457] According to the present invention, a vertically aligned liquid crystal cured film can be directly formed without forming a vertically aligned film on a substrate. In addition, it was confirmed that since the substrate and the vertically aligned liquid crystal cured film have the most suitable adhesion, when a laminated body including the vertically aligned liquid crystal cured film is cut, the vertically aligned liquid crystal cured film is not easily peeled off from the substrate, and when the substrate is peeled off from the laminated body, it can be peeled off with a small force.
[0458] Description of Reference Numerals
[0459] 1: Base material
[0460] 2: Vertically oriented liquid crystal curing film
[0461] 11: Laminated body
[0462] a: Interface on the substrate side
[0463] b: Non-substrate side interface
Claims
1. A laminate comprising a substrate and a vertically aligned liquid crystal cured film adjacent to the substrate, The vertical alignment liquid crystal cured film is a cured product of a polymerizable liquid crystal composition comprising at least one vertical alignment promoter and at least one polymerizable liquid crystal compound. The polymerizable liquid crystal composition further comprises a compound having a functional group capable of reacting with a hydroxyl group or a carboxyl group and a (meth)acryloyl group in the molecule, and an ionic compound. The compound having a functional group capable of reacting with a hydroxyl group or a carboxyl group and a (meth)acryloyl group in the molecule is a compound obtained by reacting a first compound having a functional group capable of reacting with a hydroxyl group or a carboxyl group and an amino group in the molecule and a second compound having a (meth)acryloyl group and an isocyanate group in the molecule. The functional group capable of reacting with a hydroxyl group or a carboxyl group is selected from at least one of the group consisting of an isocyanate group, an epoxy group, an oxetane group, a silanol group, an alkoxysilyl group and a hydroxysilyl group, The ionic compound satisfies the following formula (4): 5<M<16 (4) In formula (4), M is represented by the following formula (5): M = (the number of covalent bonds from the positively charged atom to the molecular chain terminal of the substituent with the largest number of covalent bonds to the molecular chain terminal among the substituents directly bonded to the positively charged atom) ÷ (the number of positively charged atoms) (5), The molecular weight of the ionic compound is 100 or more and 3000 or less, Furthermore, the vertically aligned liquid crystal cured film is a liquid crystal cured film in which the polymerizable liquid crystal compound is cured in a state of being aligned in a vertical direction relative to the plane of the liquid crystal cured film. The laminate satisfies the formula (1), 0.02 <P<1.00 (N / 25mm) (1) In the formula (1), P is a substrate peeling force (N / 25 mm) when the substrate is peeled off at a rate of 300 mm / min at the interface between the vertically aligned liquid crystal cured film and the substrate constituting the laminate.
2. The laminate according to claim 1, wherein The film thickness of the vertically aligned liquid crystal cured film is 0.3 μm or more and 5.0 μm or less.
3. The laminate according to claim 1 or 2, wherein: The vertically aligned liquid crystal cured film satisfies the formula (2), -150nm≤RthC(550)≤-30nm (2) In the formula (2), RthC(550) represents the retardation value in the thickness direction at a wavelength of 550 nm of the vertically aligned liquid crystal cured film.
4. The laminate according to any one of claims 1 to 3, wherein The polymerizable liquid crystal compound has a (meth)acryloyl group as a polymerizable group.
5. The laminate according to any one of claims 1 to 4, wherein The vertical alignment liquid crystal cured film contains an ionic compound composed of non-metal atoms as a vertical alignment accelerator.
6. The laminate according to claim 5, wherein The molecular weight of the ionic compound formed of the non-metal atom is 100 or more and 10,000 or less.
7. The laminate according to any one of claims 1 to 6, wherein The polymerizable liquid crystal composition for forming a vertically aligned liquid crystal cured film comprises at least one vertical alignment promoter, at least one polymerizable liquid crystal compound having a (meth)acryloyl group, and at least one polymerizable non-liquid crystal compound having two or more (meth)acryloyl groups.
8. The laminate according to any one of claims 1 to 7, wherein The vertical alignment liquid crystal cured film contains a nonionic silane compound as a vertical alignment accelerator.
9. The laminate according to claim 8, wherein: The nonionic silane compound is a silane coupling agent.
10. The laminate according to any one of claims 1 to 4, wherein The vertical alignment liquid crystal cured film contains a nonionic silane compound and an ionic compound composed of non-metal atoms as a vertical alignment accelerator.
11. The laminate according to any one of claims 1 to 10, wherein The vertically aligned liquid crystal cured film satisfies the following relational expression (3): RthC(450) / RthC(550)≤1.0 (3) In formula (3), RthC(450) represents the retardation value in the thickness direction of the vertically aligned liquid crystal cured film at a wavelength of 450 nm, and RthC(550) represents the retardation value in the thickness direction of the vertically aligned liquid crystal cured film at a wavelength of 550 nm. 12 . The laminate according to claim 1 , further comprising a horizontally aligned phase difference film.
13. The laminate according to claim 12, wherein The horizontally aligned phase difference film is a horizontally aligned liquid crystal cured film obtained by curing at least one polymerizable liquid crystal compound in a state of being horizontally aligned with respect to the in-plane direction of the phase difference film. An elliptically polarizing plate comprising a polarizing film and the laminate according to claim 12 or 13.
15. The elliptically polarizing plate according to claim 14, wherein: The angle formed by the slow axis of the horizontally aligned phase difference film and the absorption axis of the polarizing film was 45±5°. 16 . An organic EL display device comprising the elliptically polarizing plate according to claim 14 .
17. A composition for forming a vertically aligned liquid crystal cured film, comprising: A compound having a functional group capable of reacting with a hydroxyl group or a carboxyl group and a (meth)acryloyl group in the molecule; a polymerizable liquid crystal compound; and Ionic compounds composed of non-metal atoms as vertical alignment promoters, The vertical alignment liquid crystal cured film-forming composition may further include a polymerizable non-liquid crystal compound having two or more (meth)acryloyl groups in a molecule. The compound having a functional group capable of reacting with a hydroxyl group or a carboxyl group and a (meth)acryloyl group in the molecule is a compound obtained by reacting a first compound having a functional group capable of reacting with a hydroxyl group or a carboxyl group and an amino group in the molecule and a second compound having a (meth)acryloyl group and an isocyanate group in the molecule. The functional group capable of reacting with a hydroxyl group or a carboxyl group is selected from at least one of the group consisting of an isocyanate group, an epoxy group, an oxetane group, a silanol group, an alkoxysilyl group and a hydroxysilyl group, The molecular weight of the ionic compound is 100 or more and 3000 or less, and the ionic compound satisfies the following formula (4): 5<M<16 (4) In formula (4), M is represented by the following formula (5): M = (the number of covalent bonds from the atom having a positive charge to the molecular chain terminal of the substituent having the largest number of covalent bonds to the molecular chain terminal among the substituents directly bonded to the atom having a positive charge) ÷ (the number of atoms having a positive charge) (5).
18. The composition for forming a vertically aligned liquid crystal cured film according to claim 17, wherein The polymerizable liquid crystal compound is a polymerizable liquid crystal compound having a (meth)acryloyl group.
Citation Information
Patent Citations
Compound, optical film, and manufacturing method for optical film
JP2009173893A
Compound, optical film, and method for producing optical film
JP2010031223A
compound
JP2010270108A
Compound, optical film and method for producing optical film
JP2011006360A
Compound, optical film and method for producing optical film
JP2011207765A